Composite cathode active material and All Solid secondary battery comprising composite cathode active material
Patent Information
- Application Number
- KR1020230078212
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-06-19
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2043-06-19
Smart Images

Figure 112023067115650-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The invention relates to a composite cathode active material, a cathode containing the same, and an all-solid-state secondary battery. Background Technology
[0002] Recently, driven by industrial demands, the development of batteries with high energy density and safety is actively underway. For example, lithium batteries are used in various applications, including information devices, communication equipment, and automobiles. Since automobiles are a matter of life and death, safety is also critical.
[0003] Lithium batteries using liquid electrolytes may have an increased risk of fire and / or explosion in the event of a short circuit. All-solid-state secondary batteries employing solid electrolytes instead of liquid electrolytes are being proposed. Solid electrolytes have a lower risk of ignition compared to liquid electrolytes.
[0004] All-solid-state secondary batteries can reduce the possibility of fire or explosion by employing a solid electrolyte instead of a liquid electrolyte. All-solid-state batteries can provide enhanced safety. The problem to be solved
[0005] One aspect is to provide a composite cathode active material that offers improved capacity and cycle characteristics by having a reduced crystallite size.
[0006] Another aspect is to provide a cathode comprising the above-mentioned composite cathode active material.
[0007] Another aspect is to provide an all-solid-state secondary battery comprising the above-mentioned anode. means of solving the problem
[0008] According to one embodiment
[0009] It includes a composite of M2S, alkali metal salts, and carbon-based materials,
[0010] The above M is an alkali metal, and the alkali metal is Li or Na,
[0011] The size of the M2S crystallites obtained from the XRD spectrum of the above complex is less than 9.9 nm, and
[0012] A composite cathode active material is provided, wherein the above composite comprises a solid solution of M2S and an alkali metal salt.
[0013] According to another embodiment,
[0014] A positive current collector; and a positive active material layer disposed on one or both sides of the positive current collector, comprising
[0015] A cathode is provided in which the above-described cathode active material layer comprises the above-described composite cathode active material and sulfide-based solid electrolyte.
[0016] According to another embodiment,
[0017] A positive electrode according to the above; a negative electrode; and an electrolyte layer disposed between the positive electrode and the negative electrode,
[0018] An all-solid-state secondary battery is provided, wherein the above-mentioned negative electrode comprises a negative electrode current collector and a first negative electrode active material layer disposed on one surface of the above-mentioned negative electrode current collector.
[0019] According to other work implementation examples
[0020] A positive electrode according to the above; a negative electrode; and an electrolyte layer disposed between the positive electrode and the negative electrode,
[0021] An all-solid-state secondary battery is provided, wherein the anode comprises the composite anode active material described above. Effects of the invention
[0022] According to one aspect, it is possible to provide an all-solid-state secondary battery having increased capacity and improved cycle characteristics by providing a composite cathode active material having a reduced crystallite size. Brief explanation of the drawing
[0023] Figure 1 shows the XRD spectra of ground Li2S, the Li2S-LiI composite which is the intermediate product of Example 1, and the Li2S-LiI-CNF composite prepared in Example 1. Figure 2a is a scanning electron microscope image of Li2S used in Example 1. Figure 2b is the XRD spectrum of the Li2S-LiI-CNF composite prepared in Example 1. FIG. 3 is a cross-sectional view of an all-solid-state secondary battery according to an exemplary embodiment. FIG. 4 is a cross-sectional view of an all-solid-state secondary battery according to an exemplary embodiment. FIG. 5 is a cross-sectional view of an all-solid-state secondary battery according to an exemplary embodiment. FIG. 6 is a cross-sectional view of an all-solid-state secondary battery according to an exemplary embodiment. FIG. 7 is a cross-sectional view of an all-solid-state secondary battery according to an exemplary embodiment. Specific details for implementing the invention
[0024] Unless otherwise defined, all terms used in this disclosure (including technical and scientific terms) have the same meaning as generally understood by those skilled in the art to which this disclosure pertains. Additionally, terms as defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning within the context of the relevant technology and this disclosure, and should not be interpreted in an idealized or overly formal sense.
[0025] Exemplary embodiments are described in this disclosure with reference to cross-sectional views, which are schematic diagrams of idealized embodiments. As such, variations from the depicted shapes should be expected as a result of, for example, manufacturing techniques and / or tolerances. Accordingly, the embodiments described in this disclosure should not be interpreted as being limited to the specific shapes of the regions as depicted in this disclosure, but should include variations in shapes resulting from, for example, manufacturing. For example, a region depicted or described as flat may typically have rough and / or non-linear features. Furthermore, an angle depicted as sharp may be rounded. Accordingly, the regions depicted in the drawings are essentially schematic, and the shapes are not intended to depict the exact shape of the region and are not intended to limit the scope of the claims.
[0026] The present creative idea may be embodied in many different forms and should not be interpreted as being limited to the embodiments described in this disclosure. Embodiments are provided to ensure that this disclosure is made thorough and complete, and to fully convey the scope of the present creative idea to those skilled in the art. Identical reference numerals denote identical components.
[0027] When it is stated that one component is "on top" of another component, it can be understood that it may be directly on top of the other component or that another component may be interposed between them. In contrast, when it is stated that a component is "directly on top" of another component, no component is interposed between them.
[0028] Terms such as “first,” “second,” “third,” etc., may be used in this disclosure to describe various components, components, regions, layers, and / or zones, but these components, components, regions, layers, and / or zones should not be limited by these terms. These terms are used solely to distinguish one component, component, region, layer, or zone from another. Accordingly, the first component, component, region, layer, or zone described below may be referred to as the second component, component, region, layer, or zone without departing from the teachings of this disclosure.
[0029] The terms used in this disclosure are intended to describe specific embodiments only and are not intended to limit the creative idea. Unless the content clearly indicates otherwise, the singular form used herein is intended to include the plural form including “at least one.” “At least one” should not be interpreted as limiting to the singular. As used in this disclosure, the term “and / or” includes any combination of one or more of the listed items. The terms “comprising” and / or “comprising” as used in the detailed description specify the presence of the specified features, regions, integers, steps, actions, components, and / or components, and do not exclude the presence or addition of one or more other features, regions, integers, steps, actions, components, components, and / or groups thereof.
[0030] Spatially relative terms such as "bottom," "lower," "lower," "top," "upper," and "upper" may be used herein to facilitate the description of the relationship of one component or feature to another component or feature. Spatially relative terms are to be understood as intended to include different orientations of the device in use or operation in addition to the orientations depicted in the drawings. For example, if the device in the drawings is inverted, the component described as "bottom" or "lower" of another component or feature will be oriented to the "upper" of the other component or feature. Thus, the exemplary term "bottom" may encompass both the upper and lower directions. The device may be positioned in different directions (it may be rotated 90 degrees or rotated in other directions), and the spatially relative terms used in this disclosure may be interpreted accordingly.
[0031] "Group" refers to a group of elements in the periodic table according to the International Union of Pure and Applied Chemistry ("IUPAC") group classification system of groups 1-18.
[0032] In the present disclosure, "particle diameter" refers to the average diameter when the particle is spherical and the average major axis length when the particle is non-spherical. The particle diameter can be measured using a particle size analyzer (PSA). "Particle diameter" is, for example, the average particle diameter. The "average particle diameter" is, for example, D50, the median particle diameter.
[0033] D50 is the particle size corresponding to 50% of the cumulative volume calculated from the side of the particle with the smaller particle size in the particle size distribution measured by laser diffraction.
[0034] D90 is the particle size corresponding to the 90% cumulative volume calculated from the side of the particle with the smaller particle size in the particle size distribution measured by laser diffraction.
[0035] D10 is the particle size corresponding to the 10% cumulative volume calculated from the side of the particle with the smaller particle size in the particle size distribution measured by laser diffraction.
[0036] In the present disclosure, “metal” includes both metals and metalloids such as silicon and germanium in an elemental or ionic state.
[0037] In this disclosure, "alloy" means a mixture of two or more metals.
[0038] In the present disclosure, "electrode active material" refers to an electrode material capable of undergoing lithiation and delithiation.
[0039] In the present disclosure, "anode active material" refers to an anode material capable of undergoing lithiation and delithiation.
[0040] In the present disclosure, "anode active material" refers to an anode material capable of undergoing lithiation and delithiation.
[0041] In the present disclosure, "lithiation" and "to lithiate" refer to the process of adding lithium to an electrode active material.
[0042] In the present disclosure, "delithiation" and "to delithiate" refer to the process of removing lithium from an electrode active material.
[0043] In this disclosure, "charge" and "to charge" refer to the process of providing electrochemical energy to a battery.
[0044] In this disclosure, "discharge" and "discharge" refer to the process of removing electrochemical energy from a battery.
[0045] In this disclosure, "anode" and "cathode" refer to electrodes where electrochemical reduction and lithiation occur during the discharge process.
[0046] In this disclosure, "cathode" and "anode" refer to electrodes where electrochemical oxidation and delithiation occur during the discharge process.
[0047] Although specific embodiments have been described, alternatives, modifications, variations, improvements, and substantial equivalents that are not currently anticipated or cannot be anticipated may arise to the applicant or those skilled in the art. Accordingly, the appended claims, which may be filed and modified, are intended to include all such alternatives, modifications, variations, improvements, and substantial equivalents.
[0048] A composite cathode active material according to exemplary embodiments and a cathode and an all-solid-state secondary battery including the same will be described in more detail below.
[0049] [Composite Cathode Active Material]
[0050] A composite cathode active material according to one embodiment comprises a composite of M2S, an alkali metal salt, and a carbon-based material. M is an alkali metal. The alkali metal is Li or Na. M2S is, for example, Li2S or Na2S. The size of the M2S crystallite obtained from the XRD spectrum of the composite is less than 9.9 nm. The size of the M2S crystallite obtained from the XRD spectrum of the composite is, for example, 9.85 nm or less, 9.83 nm or less, 9.8 nm or less, 9.5 nm or less, 9.0 nm or less, or 8.5 nm or less. The composite comprises a solid solution of M2S and an alkali metal salt. The size of the M2S crystallites obtained from the XRD spectrum of the complex is, for example, less than 1 to 9.9 nm, 1 to 9.8 nm, 2 to 9.8 nm, 2 to 9.5 nm, 2 to 9.0 nm, 2 to 8.5 nm, or 3 to 8.5 nm. The complex comprises a solid solution of M2S and an alkali metal salt.
[0051] The ionic conductivity and electronic conductivity of M2S can be simultaneously improved by forming a composite with alkali metal salts and carbon-based materials. By including alkali metal salts in the composite, the ionic conductivity of the composite cathode active material can be improved, and the internal resistance of the cathode and lithium battery containing the composite cathode active material can be reduced. By including carbon-based materials in the composite, the electronic conductivity of the composite cathode active material can be improved, and the internal resistance of the cathode and lithium battery containing the composite cathode active material can be reduced.
[0052] The composite contains M2S crystallites, and as the size of the M2S crystallites is reduced to 21 nm or less, the volume change of the M2S crystallites during charging and discharging can be mitigated. For example, as the size of the M2S crystallites decreases, the volume change caused by a single M2S crystallite is reduced, so the overall volume change of the composite during charging and discharging can be mitigated. For example, as the size of the M2S crystallites decreases, the grain boundaries between multiple M2S crystallites can more easily accommodate the volume change of the M2S crystallites during charging and discharging, so the volume change of the composite during charging and discharging can be mitigated. The possibility of defects such as cracks occurring due to volume changes in the composite during charging and discharging can be reduced. By including such a composite in the composite cathode active material, the cycle characteristics of a secondary battery containing the composite cathode active material can be improved. For example, the lifespan characteristics of a lithium battery containing such a composite cathode active material are improved.
[0053] The composite contains M2S crystallites, and as the size of the M2S crystallites is reduced to 21 nm or less, the contact area between the M2S crystallites and the alkali metal salt and / or carbon-based material can be further increased. As the contact area between the M2S crystallites and the alkali metal salt and / or carbon-based material increases, the ionic conductivity and / or cell conductivity of the composite can be further improved. Since the composite cathode active material contains such a composite, the reversibility of the electrode reaction in a secondary battery containing the composite cathode active material can be improved. Consequently, the specific capacity of the composite cathode active material can be increased.
[0054] The ionic conductivity of the composite can be increased by including a solid solution of M2S and an alkali metal salt. For example, since the solid solution of M2S and an alkali metal salt contains alkali metal ions disposed within the crystallites of M2S, the ionic conductivity of the solid solution of M2S and an alkali metal salt can be improved compared to the ionic conductivity of M2S. Consequently, the ionic conductivity of the composite can be improved and the internal resistance of the composite can be reduced. By including such a composite in the composite cathode active material, the cycle characteristics of a secondary battery containing the composite cathode active material can be improved. For example, the high-rate characteristics of a secondary battery containing such a composite cathode active material can be improved.
[0055] Li2S-alkali metal salt-carbon-based material composites are distinguished from simple mixtures of Li2S, alkali metal salts, and carbon-based materials. Simple mixtures of Li2S, alkali metal salts, and carbon-based materials fail to maintain a dense interface between them, resulting in high interfacial resistance and consequently degrading the lifespan characteristics of secondary batteries.
[0056] The composite contains M2S. Since M2S has a high theoretical capacity, it can provide a secondary battery with high energy density. However, since M2S has low ionic conductivity and / or electronic conductivity, a composite is formed with an alkali metal salt and a carbon-based material to overcome these disadvantages. The content of M2S in the composite may be, for example, 10 to 80 wt%, 20 to 70 wt%, 30 to 60 wt%, or 40 to 60 wt% of the total weight of the composite. If the content of M2S increases excessively, it may not be easy to improve the ionic conductivity and / or electronic conductivity of M2S. If the content of M2S is excessively low, the energy density of the secondary battery may decrease.
[0057] The complex comprises an alkali metal salt. The alkali metal salt is, for example, a compound that does not contain sulfur (S). The alkali metal salt may be, for example, a binary compound or a ternary compound. The alkali metal salt may be, for example, a binary compound composed of an alkali metal and one element selected from Groups 13 through 17 of the periodic table. The alkali metal salt may be, for example, a ternary compound composed of an alkali metal and two elements selected from Groups 13 through 17 of the periodic table.
[0058] The alkali metal salt may be, for example, a lithium salt. The lithium salt binary compound may include, for example, LiI, LiBr, LiCl, LiF, LiH, Li2O, Li2Se, Li2Te, Li3N, Li3P, Li3As, Li3Sb, Li3Al2, LiB3, or a combination thereof. The lithium salt ternary compound may include, for example, Li3OCl, LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiNO3, Li2CO3, LiBH4, Li2SO4, Li3BO3, Li3PO4, Li4NCl, Li5NCl2, Li3BN2, or a combination thereof. The ionic conductivity of the complex may be further enhanced by the inclusion of such lithium salts in the complex. Such lithium salts may more readily form a solid solution with Li2S within the complex, for example.
[0059] The alkali metal salt may be, for example, a sodium salt. Sodium salt binary compounds may include, for example, NaI, NaBr, NaCl, NaF, Na2O, Na2Se, Na3N, Na3P, Na3As, Na3Sb, Na3Al2, NaB3, or a combination thereof. Sodium salt ternary compounds may include, for example, Na3OCl, NaBF4, NaPF6, NaAsF6, NaClO4, NaNO3, NaAlO2, NaAlCl4, NaNO3, Na2CO3, NaBH4, Na2SO4, Na3BO3, Na3PO4, Na4NCl, Na5NCl2, Na3BN2, or a combination thereof. The ionic conductivity of the complex may be further enhanced by the inclusion of such sodium salts. These sodium salts may more readily form a solid solution with Na2S within the complex, for example.
[0060] The content of the alkali metal salt in the composite may be 1 to 40 wt%, 5 to 35 wt%, 10 to 35 wt%, 15 to 35 wt%, 20 to 35 wt%, or 25 to 35 wt% of the total weight of the composite. If the content of the alkali metal salt increases excessively, the energy density of the secondary battery may decrease. If the content of the alkali metal salt is excessively low, the ionic conductivity of the composite decreases, and the internal resistance of the composite cathode active material may increase. Consequently, the cycle characteristics of the secondary battery may deteriorate.
[0061] The molar ratio of M2S to alkali metal salt in the composite may be, for example, 50:50 to 95:5, 60:40 to 95:5, 60:40 to 90:10, 65:35 to 90:10, 65:35 to 85:15, or 70:30 to 85:15. The molar ratio of M2S to alkali metal salt in the composite may be, for example, 50:50 to 95:5, 50:50 to 90:10, 50:50 to 85:15, 50:50 to 80:20, 50:50 to 75:25, or 50:50 to 70:30. By having molar ratios of M2S and alkali metal salt within these ranges, the cycle characteristics of a secondary battery containing a composite cathode active material can be further improved. If the molar ratio of M2S is excessively high, the effect of improving ion conductivity by alkali metal salts may be negligible. If the molar ratio of M2S is excessively high, the energy density of a secondary battery containing a composite cathode active material may decrease.
[0062] The molar ratio of Li2S to lithium salt in the composite may be, for example, 50:50 to 95:5, 60:40 to 95:5, 60:40 to 90:10, 65:35 to 90:10, 65:35 to 85:15, or 70:30 to 85:15. The molar ratio of Li2S to lithium salt in the composite may be, for example, 50:50 to 95:5, 50:50 to 90:10, 50:50 to 85:15, 50:50 to 80:20, 50:50 to 75:25, or 50:50 to 70:30. By having the molar ratio of Li2S and lithium salt within these ranges, the cycle characteristics of a lithium battery containing the composite cathode active material can be further improved. If the molar ratio of Li2S is excessively high, the effect of improving ion conductivity by the lithium salt may be negligible. If the molar ratio of Li2S is excessively high, the energy density of a lithium battery containing a composite cathode active material may decrease.
[0063] The molar ratio of Na2S to sodium salt in the composite may be, for example, 50:50 to 95:5, 60:40 to 95:5, 60:40 to 90:10, 65:35 to 90:10, 65:35 to 85:15, or 70:30 to 85:15. The molar ratio of Na2S to sodium salt in the composite may be, for example, 50:50 to 95:5, 50:50 to 90:10, 50:50 to 85:15, 50:50 to 80:20, 50:50 to 75:25, or 50:50 to 70:30. By having the molar ratio of Na2S and sodium salt within these ranges, the cycle characteristics of a sodium battery containing the composite cathode active material can be further improved. If the molar ratio of Na2S is excessively high, the effect of improving ion conductivity by sodium salt may be negligible. If the molar ratio of Na2S is excessively high, the energy density of a sodium battery containing a composite cathode active material may decrease.
[0064] The composite comprises a carbon-based material. The carbon-based material may be any material containing carbon atoms, for example, used as a conductive material in the relevant art field. The carbon-based material may be, for example, crystalline carbon, amorphous carbon, or a combination thereof. The carbon-based material may be, for example, a calcined product of a carbon precursor. The carbon-based material may be, for example, a carbon nanostructure. The carbon nanostructure may be, for example, a one-dimensional carbon nanostructure, a two-dimensional carbon nanostructure, a three-dimensional carbon nanostructure, or a combination thereof. The carbon nanostructure may be, for example, a carbon nanotube, a carbon nanofiber, a carbon nanobelt, a carbon nanorod, graphene, or a combination thereof. The carbon-based material may be, for example, a porous carbon-based material or a non-porous carbon-based material. The porous carbon-based material may include, for example, periodic and regular two-dimensional or three-dimensional pores. Porous carbon-based materials may be, for example, carbon black such as Ketjen black, acetylene black, Denka black, thermal black, and channel black; graphite, activated carbon, or a combination thereof. The form of the carbon-based material may be, for example, particle form, sheet form, flake form, etc., but is not limited to these; any carbon-based material used in the relevant technical field is possible.
[0065] The content of the carbon-based material included in the composite may be, for example, 1 to 20 wt%, 5 to 20 wt%, or 10 to 20 wt% of the total weight of the composite. If the content of the carbon-based material increases excessively, the energy density of the secondary battery may decrease. If the content of the carbon-based material decreases excessively, the electronic conductivity of the composite decreases, and the internal resistance of the composite cathode active material may increase. Consequently, the cycle characteristics of the secondary battery may deteriorate.
[0066] For example, in the XRD spectrum of the composite, the first lattice constant (d1) derived from the first peak appearing at a diffraction angle 2θ = 27° ± 2.0° corresponding to the (111) crystal plane of M2S may be larger than the second lattice constant (d2) derived from the second peak appearing at a diffraction angle 2θ = 27° ± 2.0° corresponding to the (111) crystal plane of M2S in the XRD spectrum of the M2S used to manufacture the composite. Since the M2S-alkali metal salt-carbon-based material composite has a larger lattice constant (d) compared to the M2S used to manufacture the composite, alkali metal ions can be more easily transported within the M2S crystal structure of the composite. The ionic conductivity of the composite cathode active material containing the composite may be further improved. The internal resistance of the secondary battery containing the composite cathode active material may be reduced and the cycle characteristics may be improved. The difference between the first lattice constant (d1) and the second lattice constant (d2) may be 0.05 or more, 0.1 or more, 0.15 or more, 0.2 or more, or 0.25 or more. The magnitude of the first lattice constant (d1) may be, for example, 5.78 or more, 5.80 or more, 5.82 or more, 5.85 or more, 5.90 or more, 5.95 or more, or 6.0 or more. As the composite has such a magnitude of the first lattice constant (d1), the ion conductivity of the composite cathode active material containing the composite may be further improved. The internal resistance of the secondary battery containing the composite cathode active material may be reduced and the cycle characteristics may be improved.
[0067] For example, in the XRD spectrum of the composite, a first peak appearing at a diffraction angle 2θ = 27° ± 2.0° corresponding to the (111) crystal plane of M2S has a first diffraction angle, and in the XRD spectrum of M2S used to manufacture the composite, a second peak appearing at a diffraction angle 2θ = 27° ± 2.0° corresponding to the (111) crystal plane of M2S has a second diffraction angle, and the first diffraction angle may be smaller than the second diffraction angle. For example, the position of the first peak may shift to a lower angle compared to the position of the second peak. Therefore, the M2S-alkali metal salt-carbon-based material composite may have a reduced crystallite size compared to the M2S used to manufacture the composite. Since the M2S-alkali metal salt-carbon-based material composite has a reduced crystallite size, the volume change of crystallites during charging and discharging is reduced; therefore, the volume change during charging and discharging of a composite containing multiple crystallites can be mitigated. Consequently, the occurrence of defects such as cracking during charging and discharging of a composite cathode active material containing such a composite can be suppressed. As a result, the cycle characteristics of a secondary battery containing the composite cathode active material can be improved.
[0068] For example, in the XRD spectrum of the composite, a first peak appearing at a diffraction angle 2θ = 27° ± 2.0° corresponding to the (111) crystal plane of M2S has a first full width at half maximum (FWHM1), and in the XRD spectrum of M2S used to manufacture the composite, a second peak appearing at a diffraction angle 2θ = 27° ± 2.0° corresponding to the (111) crystal plane of M2S has a second full width at half maximum (FWHM2), and the first full width at half maximum may be larger than the second full width at half maximum. Therefore, the M2S-alkali metal salt-carbon-based material composite may have increased lattice strain compared to the M2S used to manufacture the composite. For example, the M2S-alkali metal salt-carbon-based material composite may have increased lattice strain by forming a solid solution with the alkali metal salt. Since the M2S-alkali metal salt-carbon-based material composite has an increased full width at half maximum (FWHM) compared to the M2S used in the composite manufacturing, the ionic conductivity of the composite cathode active material containing the composite can be further enhanced. The internal resistance of the secondary battery containing the composite cathode active material can be reduced, and the cycle characteristics can be improved.
[0069] The first full width at half maximum (FWHM) may be, for example, 1° or more, 1.05° or more, 1.10° or more, or 1.15° or more. By having the first full width at half maximum (FWHM1) of this range, the ion conductivity of the composite cathode active material containing the composite may be further improved. The internal resistance of the secondary battery containing the composite cathode active material may be reduced and the cycle characteristics may be improved.
[0070] The Mohs hardness of alkali metal salts and carbon-based materials may each be greater than that of M2S. The Mohs hardness of M2S is, for example, 0.6 or less. The Mohs hardness of Li2S is, for example, 0.6.
[0071] The Mohs hardness of the alkali metal salt may be 0.7 or higher, 0.8 or higher, 0.9 or higher, 1.0 or higher, 1.5 or higher, or 2.0 or higher. Since the alkali metal salt has a Mohs hardness within this range, the grinding of M2S can be performed more easily during the milling process, and a solid solution of M2S and the alkali metal salt can be formed more easily. The Mohs hardness of LiI is, for example, 2.0. The Mohs hardness of NaI is, for example, 2.1.
[0072] The Mohs hardness of the carbon-based material may be 0.7 or higher, 0.8 or higher, 0.9 or higher, 1.0 or higher, 1.2 or higher, or 1.5 or higher, respectively. Since the carbon-based material has a Mohs hardness within this range, the grinding of M2S can be performed more easily during the milling process, and M2S-alkali metal salt-carbon-based material composites can be easily formed. The Mohs hardness of the carbon nanofiber (CNF) is, for example, 1.5.
[0073] The particle size of the composite cathode active material, that is, the size of the composite particles, may be, for example, 2 μm or less, 1.5 μm or less, or 1 μm or less. The size of the composite particles may be, for example, 0.1 to 2 μm, 0.1 to 1.5 μm, or 0.1 to 1 μm or less. Since the volume change during charging and discharging is suppressed by the composite particles having a size within this range, the degradation of the composite cathode active material containing the composite during charging and discharging can be suppressed. If the size of the composite particles increases excessively, the degradation of the composite cathode active material containing the composite may be accelerated due to the increased volume change of the composite during charging and discharging. Consequently, the cycle characteristics of a secondary battery containing such a composite cathode active material may be degraded.
[0074] Therefore, the cycle characteristics, such as lifespan characteristics, of a secondary battery containing a composite cathode active material can be improved. The size of the composite particles, for example, the particle diameter of the composite, can be measured using a laser diffraction detector, a scanning electron microscope, etc. The particle diameter of the composite is, for example, the arithmetic mean of the particle diameters of multiple particles measured using software from a scanning electron microscope image.
[0075] The composite includes a carbon-based material, and the carbon-based material may include, for example, a fibrous carbon-based material. By including a fibrous carbon-based material, the electronic conductivity of the composite can be further enhanced. By including a fibrous carbon-based material, electronic conduction from the surface to the interior of the composite can be performed more easily. The internal resistance of the composite cathode active material containing the composite is reduced, and the cycle characteristics of the secondary battery containing the composite cathode active material can be further improved.
[0076] The aspect ratio of the fibrous carbon-based material may be, for example, 2 or more, 3 or more, 4 or more, 5 or more, 10 or more, or 20 or more. The aspect ratio of the fibrous carbon-based material may be, for example, 2 to 30, 3 to 30, 4 to 30, 5 to 30, 10 to 30, or 20 to 30. The aspect ratio of the fibrous carbon-based material may be, for example, 2 to 30, 2 to 20, 2 to 10, 2 to 8, 2 to 5, or 2 to 4. By having the fibrous carbon-based material have an aspect ratio within this range, the overall electronic conductivity of the composite is improved, and local imbalances in electronic conductivity within the composite can be further alleviated.
[0077] Fibrous carbon-based materials may include, for example, carbon nanostructures. Carbon nanostructures may include, for example, carbon nanofibers (CNF), carbon nanotubes (CNT), carbon nanobelts, carbon nanorods, or combinations thereof.
[0078] Carbon nanostructures can form a primary carbon nanostructure composed of a single carbon nanostructure and a secondary carbon nanostructure composed of multiple aggregated carbon nanostructures.
[0079] The diameter of the primary carbon nanostructure may be, for example, 1 nm to 200 nm, 1 nm to 150 nm, 1 nm to 100 nm, 1 nm to 50 nm, 1 nm to 30 nm, or 1 nm to 20 nm. The length of the primary carbon nanostructure may be, for example, 10 nm to 2 µm, 10 nm to 1.5 µm, 10 nm to 1 µm, 10 nm to 500 nm, 10 nm to 400 nm, 10 nm to 300 nm, 10 nm to 200 nm, or 10 nm to 100 nm. The diameter and length of the primary carbon nanostructure may be measured from scanning electron microscope (SEM) or transmission electron microscope (TEM) images. Alternatively, the diameter and / or length of the primary carbon nanostructure may be measured by laser diffraction.
[0080] A secondary carbon nanostructure is a structure formed by assembling, for example, primary carbon nanostructures to form a bundle or rope type, either wholly or partially. The secondary carbon nanostructure may include, for example, bundle-type carbon nanostructures, rope-type carbon nanostructures, or a combination thereof. The diameter of the secondary carbon nanostructure may be, for example, 2 nm to 200 nm, 3 nm to 150 nm, 5 nm to 100 nm, 5 nm to 50 nm, 5 nm to 30 nm, or 5 nm to 20 nm. The length of the secondary carbon nanotube structure may be, for example, 20 nm to 2 µm, 30 nm to 1.5 µm, 50 nm to 1 µm, 50 nm to 500 nm, 50 nm to 400 nm, 50 nm to 300 nm, 50 nm to 200 nm, or 50 nm to 100 nm or more. The diameter and length of the secondary carbon nanostructure can be measured from scanning electron microscope (SEM) images or optical microscopes. Alternatively, the diameter and / or length of the secondary carbon nanostructure can be measured by laser diffraction. The secondary carbon nanostructure can be converted into a primary carbon nanostructure by dispersing it in a solvent, for example, and then used to manufacture a composite.
[0081] For 100 parts by weight of the composite, it may include, for example, 10 to 80 parts by weight of M2S, 1 to 40 parts by weight of an alkali metal salt, and 1 to 20 parts by weight of a carbon-based material. The M2S content included in the composite may, for example, be 10 to 80 parts by weight, 20 to 70 parts by weight, 30 to 60 parts by weight, or 40 to 60 parts by weight of M2S for 100 parts by weight of the composite. The alkali metal salt content included in the composite may, for example, be 10 to 40 parts by weight, 15 to 40 parts by weight, 20 to 40 parts by weight, or 25 to 35 parts by weight of the alkali metal salt for 100 parts by weight of the composite. The carbon-based material content included in the composite may, for example, be 1 to 20 parts by weight, 5 to 20 parts by weight, or 5 to 15 parts by weight of the carbon-based material for 100 parts by weight of the composite. As the composite has a composition of M2S, alkali metal salts, and carbon-based materials within this range, the composite cathode active material containing the composite can provide excellent ionic conductivity and / or electronic conductivity.
[0082] The ionic conductivity of the complex is, for example, 1×10⁻⁶ at 25 ℃ -5 S / cm or more, 2×10 -5 S / cm or more, 4×10 -5 S / cm or more, 6×10 -5 S / cm or more, 8×10 -5 S / cm or more or 1×10 -4 It may be greater than S / cm. Ionic conductivity can be measured using, for example, electrochemical impedance spectroscopy or the DC polarization method. Since the composite has ionic conductivity within this range, the internal resistance of the composite cathode active material containing the composite may be reduced. The cycle characteristics of a secondary battery containing the composite cathode active material may be improved. The electronic conductivity of the composite is, for example, 1×10⁻⁶ at 25 ℃ -5 S / cm or more, 2×10-5 S / cm or more, 4×10 -5 S / cm or more, 6×10 -5 S / cm or more, 8×10 -5 S / cm or more or 1×10 -4 It can be greater than S / cm. Electrochemical conductivity can be measured using, for example, electrochemical impedance spectroscopy or the DC polarization method. As the composite has an electron conductivity within this range, the internal resistance of the composite cathode active material containing the composite can be reduced. The cycle characteristics of the secondary battery containing the composite cathode active material can be improved.
[0083] [anode]
[0084] [Anode: Anode active material]
[0085] A positive electrode according to one embodiment comprises a positive electrode current collector; and a positive electrode active material layer disposed on one or both sides of the positive electrode current collector. The positive electrode active material layer comprises the composite positive electrode active material and the solid electrolyte described above. By including the composite positive electrode active material and the solid electrolyte, the positive electrode may have a further reduced internal resistance. Accordingly, the cycle characteristics of a secondary battery equipped with the positive electrode may be further improved.
[0086] Referring to FIGS. 3 to 7, the anode (10) comprises an anode current collector (11); and an anode active material layer (12) disposed on one or both sides of the anode current collector (11). The anode active material layer (12) comprises the composite anode active material and solid electrolyte described above.
[0087] A composite cathode active material may be included in an amount of 40 to 90 parts by weight, 40 to 80 parts by weight, 50 to 80 parts by weight, or 50 to 70 parts by weight per 100 parts by weight of the cathode active material layer (12). If the content of the composite cathode active material is excessively reduced, the energy density of the secondary battery decreases. If the content of the composite cathode active material is excessively increased, the degradation of the cathode may be accelerated due to changes in the volume of the cathode during charging and discharging. As a result, the cycle characteristics of the secondary battery (1) may be degraded.
[0088] The positive active material layer (12) may additionally include other positive active materials in addition to the composite positive active material described above.
[0089] Other cathode active materials may include, for example, Li2S-containing composites. The Li2S composite includes, for example, a composite of Li2S and a carbon-based material, a composite of Li2S and a carbon-based material and a solid electrolyte, a composite of Li2S and a solid electrolyte, a composite of Li2S and a lithium salt, a composite of Li2S and a metal carbide, a composite of Li2S and a carbon-based material and a metal carbide, a composite of Li2S and a metal nitride, a composite of Li2S and a carbon-based material and a metal nitride, or a combination thereof.
[0090] The composite of Li2S and carbon-based materials includes carbon-based materials. The carbon-based materials refer to the carbon-based materials of the composite cathode active material described above. The method for manufacturing the composite of Li2S and carbon-based materials may be a dry method, a wet method, or a combination thereof, but is not limited thereto, and any method used in the relevant technical field is possible. The method for manufacturing the composite of Li2S and carbon-based materials may be, for example, milling, heat treatment, deposition, etc., but is not necessarily limited thereto, and any method used in the relevant technical field is possible.
[0091] The composite of Li2S, carbon-based materials, and solid electrolytes includes carbon-based materials and solid electrolytes. The carbon-based material refers to the composite of Li2S and carbon-based materials described above. The solid electrolyte may be any material used as an ion-conducting material in the relevant art field, for example. The solid electrolyte is, for example, an inorganic solid electrolyte. The solid electrolyte is, for example, a crystalline solid electrolyte, an amorphous solid electrolyte, or a combination thereof. The solid electrolyte is, for example, a sulfide-based solid electrolyte, an oxide-based solid electrolyte, or a combination thereof. The sulfide-based solid electrolyte contains, for example, Li, S, and P, and may optionally further contain halogen elements. The sulfide-based solid electrolyte may be selected from among sulfide-based solid electrolytes used in the electrolyte layer. The sulfide-based solid electrolyte is, for example, 1 × 10⁻⁶ at room temperature. -5 It can have an ionic conductivity of S / cm or greater. Oxide-based solid electrolytes include, for example, Li, O, and transition metal elements, and may optionally include other elements. Oxide-based solid electrolytes, for example, 1×10⁻⁶ at room temperature -5 It may be a solid electrolyte having an ionic conductivity of S / cm or higher. The oxide-based solid electrolyte may be selected from among oxide-based solid electrolytes used in the electrolyte layer.
[0092] The composite of Li2S and a solid electrolyte includes a solid electrolyte. The solid electrolyte refers to the composite of Li2S, a carbon-based material, and a solid electrolyte described above.
[0093] The composite of Li2S and lithium salt comprises Li2S and lithium salt. The lithium salt refers to the lithium salt of the composite cathode active material described above. The lithium salt is, in particular, one or more lithium halide compounds selected from LiF, LiCl, LiBr, and LiI. The composite of Li2S and lithium salt may be, for example, a composite of Li2 and lithium halide. The inclusion of a lithium halide compound in the composite of Li2 and lithium salt can provide enhanced ionic conductivity. The composite of Li2S and lithium salt is distinguished from a simple mixture of Li2S, a carbon-based material, and a lithium salt. A simple mixture of Li2S and lithium salt provides high interfacial resistance because it fails to maintain a dense interface between Li2S and the lithium salt, which can consequently degrade the life characteristics of the all-solid-state secondary battery.
[0094] The complex of Li2S and metal carbide contains metal carbide. The metal carbide is, for example, a two-dimensional metal carbide. The two-dimensional metal carbide is, for example, M n+1 C n T x It is expressed as (M is a transition metal, T is a terminal group, T is O, OH and / or F, n=1, 2, or 3, and x is the number of terminal groups). Two-dimensional metal carbides are, for example, Ti2CT x , (Ti 0.5 , Nb 0.5 )2CT x , Nb2CT x , V2CT x , Ti3C2T x , (V 0.5 , Cr 0.5 )3C2T x , Ti3CNT x , Ta4C3T x , Nb4C3T x Or a combination of these. The surface of a two-dimensional metal carbide is terminated by O, OH and / or F.
[0095] The composite of Li2S, carbonaceous materials, and metal carbides includes carbonaceous materials and metal carbides. The carbonaceous material refers to the composite of Li2S and carbonaceous materials described above. The metal carbide refers to the composite of Li2S and metal carbides described above.
[0096] The complex of Li2S and metal nitride contains the metal nitride. The metal nitride is, for example, a two-dimensional metal nitride. The two-dimensional metal nitride is, for example, M n+1 N n T x It is expressed as (M is a transition metal, T is a terminal group, T is O, OH and / or F, n=1, 2, or 3, and x is the number of terminal groups). The surface of a two-dimensional metal nitride is terminated by O, OH and / or F.
[0097] The composite of Li2S, carbonaceous materials, and metal nitrides includes carbonaceous materials and metal nitrides. The carbonaceous material refers to the composite of Li2S and carbonaceous materials described above. The metal carbide refers to the composite of Li2S and metal nitrides described above.
[0098] The positive active material layer (12) may additionally include a sulfide-based compound that is distinct from the positive active material described above, for example. The sulfide-based compound may be, for example, a compound containing a metal element other than Li and a sulfur element. The sulfide-based compound may be, for example, a compound containing a metal element belonging to Group 1 to Group 14 of the periodic table with an atomic weight of 10 or more and a sulfur element. The sulfide-based compound may be, for example, FeS2, VS2, NaS, MnS, FeS, NiS, CuS, or a combination thereof. By additionally including a sulfide-based compound in the positive active material layer, the cycle characteristics of the all-solid-state secondary battery may be further improved. The content of such a sulfide-based compound included in the positive active material layer (12) may be 10 wt% or less, 5 wt% or less, 3 wt% or less, or 1 wt% or less of the total weight of the positive active material layer (12).
[0099] [Anode: Solid Electrolyte]
[0100] The positive electrode active material layer (12) may further include, for example, a solid electrolyte. The solid electrolyte may be, for example, a sulfide-based solid electrolyte. The solid electrolyte included in the positive electrode (10) may be the same as or different from the solid electrolyte included in the electrolyte layer (30). For details regarding the solid electrolyte, refer to the electrolyte layer (30).
[0101] The solid electrolyte included in the positive electrode active material layer (12) may have a smaller D50 average particle size compared to the solid electrolyte included in the electrolyte layer (30). For example, the D50 average particle size of the solid electrolyte included in the positive electrode active material layer (12) may be 90% or less, 80% or less, 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, or 20% or less of the D50 average particle size of the solid electrolyte included in the electrolyte layer (30). The D50 average particle size is, for example, the median particle diameter (D50). The median particle diameter (D50) is the particle size corresponding to 50% of the cumulative volume calculated from the side of the particle having a small particle size in the particle size distribution measured, for example, by laser diffraction.
[0102] A solid electrolyte may be included in an amount of 10 to 60 parts by weight, 10 to 50 parts by weight, 20 to 50 parts by weight, or 30 to 50 parts by weight per 100 parts by weight of the positive electrode active material layer (12). If the content of the solid electrolyte is reduced excessively, the cycle characteristics of the secondary battery may be degraded as the internal resistance of the positive electrode increases. If the content of the sulfide-based solid electrolyte is increased excessively, the energy density of the secondary battery (1) may be reduced.
[0103] [Bipolar: Challenge Material]
[0104] The positive electrode active material layer (12) may further include a conductive material. The conductive material may be, for example, a carbon-based conductive material, a metal-based conductive material, or a combination thereof. The carbon-based conductive material may be, for example, graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or a combination thereof, but is not limited to these, and any material used as a carbon-based conductive material in the relevant technical field is possible. The metal-based conductive material may be metal powder, metal fiber, or a combination thereof, but is not limited to these, and any material used as a metal-based conductive material in the relevant technical field is possible. The content of the conductive material included in the positive electrode active material layer (12) may be, for example, 1 wt% to 30 wt%, 1 wt% to 20 wt%, or 1 wt% to 10 wt% of the total weight of the positive electrode active material layer (12).
[0105] The positive active material layer (12) includes a carbon-based material, and the carbon-based material may be placed only in the composite positive active material. The positive active material layer (12) may not additionally include a separate carbon-based material in addition to the composite positive active material equipped with the carbon-based material. By not including a separate carbon-based material in the positive active material layer, the energy density of the positive and secondary battery (1) can be improved and the manufacturing process can be simplified.
[0106] [Positive: Binder]
[0107] The positive active material layer (12) may further include a binder. The binder may be, for example, styrene butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, etc., but is not limited to these and any binder used in the relevant technical field may be used. The binder content included in the positive active material layer (12) may be, for example, 1 wt% to 10 wt% of the total weight of the positive active material layer (12). The binder may be omitted.
[0108] [Anode: Other Additives]
[0109] The positive active material layer (12) may further include additives such as fillers, coating agents, dispersants, and ion conductivity aids in addition to the positive active material, solid electrolyte, binder, and conductive material described above.
[0110] The filler, coating agent, dispersant, ion-conducting auxiliary agent, etc. that the positive electrode active material layer (12) may include can be any known material generally used in the electrodes of all-solid-state secondary batteries.
[0111] [Polygonal: Positive current collector]
[0112] The positive current collector (11) is made of, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or an alloy thereof, such as a plate or foil. The positive current collector (11) may be omitted. The thickness of the positive current collector (11) is, for example, 1 μm to 100 μm, 1 μm to 50 μm, 5 μm to 25 μm, or 10 μm to 20 μm.
[0113] The positive current collector (11) may include, for example, a base film and a metal layer disposed on one or both sides of the base film. The base film may include, for example, a polymer. The polymer may be, for example, a thermoplastic polymer. The polymer may include, for example, polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polybutylene terephthalate (PBT), polyimide (PI), or a combination thereof. The base film may be, for example, an insulator. By including an insulating thermoplastic polymer in the base film, the base film may soften or liquefy upon a short circuit, thereby blocking battery operation and suppressing a sudden increase in current. The metal layer may include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), or an alloy thereof. The metal layer can act as an electrochemical fuse and be cut off upon overcurrent to perform a short-circuit prevention function. The limit current and maximum current can be controlled by adjusting the thickness of the metal layer. The metal layer can be plated or deposited on the base film. As the thickness of the metal layer decreases, the limit current and / or maximum current of the positive current collector (11) decreases, thereby improving the stability of the lithium battery during a short circuit. A lead tab may be added to the metal layer for external connection. The lead tab may be welded to the metal layer or the metal layer / base film laminate by ultrasonic welding, laser welding, spot welding, etc. During welding, the base film and / or metal layer melt, allowing the metal layer to be electrically connected to the lead tab. To make the weld between the metal layer and the lead tab more robust, a metal chip may be added between the metal layer and the lead tab.The metal chip may be a thin sheet of the same material as the metal of the metal layer. The metal chip may be, for example, a metal foil, a metal mesh, etc. The metal chip may be, for example, an aluminum foil, a copper foil, a SUS foil, etc. A lead tab may be welded to a metal chip / metal layer laminate or a metal chip / metal layer / base film laminate by placing the metal chip on the metal layer and then welding it to the lead tab. During welding, the base film, the metal layer, and / or the metal chip may melt, thereby electrically connecting the metal layer or the metal layer / metal chip laminate to the lead tab. A metal chip and / or lead tab may be added to a portion of the metal layer. The thickness of the base film may be, for example, 1 to 50 μm, 1.5 to 50 μm, 1.5 to 40 μm, or 1 to 30 μm. By having the base film within this range of thickness, the weight of the electrode assembly can be reduced more effectively. The melting point of the base film may be, for example, 100 to 300 °C, 100 to 250 °C or lower, or 100 to 200 °C. Since the base film has a melting point within this range, the base film can melt during the welding process of the lead tab and be easily bonded to the lead tab. Surface treatments, such as corona treatment, may be performed on the base film to improve the adhesion between the base film and the metal layer. The thickness of the metal layer may be, for example, 0.01 to 3 μm, 0.1 to 3 μm, 0.1 to 2 μm, or 0.1 to μm. Since the metal layer has a thickness within this range, the stability of the electrode assembly can be ensured while maintaining conductivity. The thickness of the metal piece may be, for example, 2 to 10 μm, 2 to 7 μm, or 4 to 6 μm. Since the metal piece has a thickness within this range, the connection between the metal layer and the lead tab can be performed more easily. By having the positive current collector (11) have this structure, the weight of the positive electrode can be reduced and, as a result, the energy density of the positive electrode and the lithium battery can be improved.
[0114] [Polygon: Inert component]
[0115] Referring to FIGS. 6 and 7, the anode (10) comprises an anode current collector (11) and an anode active material layer (12) disposed on one side of the anode current collector. An inactive member (40) is disposed on one side of the anode (10). Referring to FIG. 6, the inactive member (40) is disposed on one side of the anode active material layer (12) and the anode current collector (11). Referring to FIG. 7, the inactive member (40) is disposed on one side of the anode active material layer (12) and is disposed between the electrolyte layer (30) and the anode current collector (11) facing the electrolyte layer (30). The inactive member (40) is not disposed on one side of the anode current collector (11). The electrolyte layer (30) may be, for example, a solid electrolyte layer.
[0116] By including an inert member (40), cracking of the electrolyte layer (30) is prevented during manufacturing and / or charging and discharging of the all-solid-state secondary battery (1), and consequently, the cycle characteristics of the all-solid-state secondary battery (2) are improved. In an all-solid-state secondary battery (1) that does not include an inert member (40), uneven pressure is applied to the electrolyte layer (30) in contact with the positive electrode (10) during manufacturing and / or charging and discharging of the all-solid-state secondary battery (1), causing cracking in the electrolyte layer (30), and the possibility of a short circuit occurring due to the growth of lithium metal through this increases.
[0117] In the all-solid-state secondary battery (1), the thickness of the inert member (40) is greater than or equal to the thickness of the positive active material layer (12). Alternatively, in the all-solid-state secondary battery (1), the thickness of the inert member (40) is substantially equal to the thickness of the positive electrode (10). Since the thickness of the inert member (40) is equal to the thickness of the positive electrode (10), a uniform pressure is applied between the positive electrode (10) and the electrolyte layer (30), and the positive electrode (10) and the electrolyte layer (30) are sufficiently in contact, thereby reducing the interfacial resistance between the positive electrode (10) and the electrolyte layer (30). Additionally, as the electrolyte layer (30) is sufficiently sintered during the pressurized manufacturing process of the all-solid-state secondary battery (1), the internal resistance of the electrolyte layer (30) and the all-solid-state secondary battery (1) containing it is reduced.
[0118] The inert member (40) surrounds the side of the anode (10) and comes into contact with the electrolyte layer (30). By the inert member (40) surrounding the side of the anode (10) and coming into contact with the electrolyte layer (30), cracks in the electrolyte layer (30) caused by pressure differences during the pressing process in the electrolyte layer (30) that does not come into contact with the anode (20) can be effectively suppressed. The inert member (40) surrounds the side of the anode (10) and is separated from the cathode (20), more specifically from the first cathode active material layer (22). The inert member (40) surrounds the side of the anode (10), comes into contact with the electrolyte layer (30), and is separated from the cathode (20). Therefore, the possibility of a short circuit occurring due to physical contact between the anode (10) and the first cathode active material layer (22), or due to overcharging of lithium, is suppressed. For example, by placing an inert member (40) on one side of the positive active material layer (12) and simultaneously placing it on one side of the positive current collector (11), the possibility of a short circuit occurring due to contact between the positive current collector (11) and the negative electrode (20) is more effectively suppressed.
[0119] Referring to FIGS. 6 and 7, the inert member (40) extends from one side of the anode (30) to the end portion of the electrolyte layer (30). By extending the inert member (40) to the end portion of the electrolyte layer (30), cracks occurring at the end portion of the electrolyte layer (30) can be suppressed. The end portion of the electrolyte layer (30) is the outermost portion that contacts the side of the electrolyte layer (30). The inert member (40) extends to the outermost portion that contacts the side of the electrolyte layer (30). The inert member (40) is separated from the cathode (20), more specifically from the first cathode active material layer (22). The inert member (40) extends to the end portion of the electrolyte layer (30) but does not come into contact with the cathode (20). The inert member (40) fills the space extending from one side of the anode (30) to the end of the electrolyte layer (30), for example.
[0120] Referring to FIGS. 6 and 7, the width of the inert member (40) extending from one side of the anode (10) to the end portion of the electrolyte layer (30) is, for example, 1 to 30%, 1 to 25%, 1 to 20%, 1 to 15%, 1 to 10%, or 1 to 5% of the width between one side of the anode (10) and the other side facing said one side. If the width of the inert member (40) is excessively large, the energy density of the all-solid-state secondary battery (1) is reduced. If the width of the inert member (40) is excessively small, the effect of placing the inert member (40) is negligible.
[0121] The area of the anode (10) is smaller than the area of the electrolyte layer (30) in contact with the anode (10). An inert member (40) is arranged to surround the side of the anode (10) to compensate for the difference in area between the anode (10) and the electrolyte layer (30). By compensating for the difference in area between the anode (10) and the electrolyte layer (30) with the area of the inert member (40), cracks in the electrolyte layer (30) caused by pressure differences during the pressing process are effectively suppressed. For example, the sum of the area of the anode (10) and the area of the inert member (40) is equal to the area of the electrolyte layer (30). The electrolyte layer (30) may be, for example, a solid electrolyte layer.
[0122] The area of the anode (10) is, for example, less than 100%, 99% or less, 98% or less, 97% or less, 96% or less, or 95% or less of the area of the electrolyte layer (30). The area of the anode (10) is, for example, 50% to less than 100%, 50% to 99%, 55% to 98%, 60% to 97%, 70% to 96%, 80% to 95%, or 85% to 95% of the area of the electrolyte layer (30).
[0123] If the area of the positive electrode (10) is equal to or larger than the area of the electrolyte layer (30), the possibility of a short circuit occurring due to physical contact between the positive electrode (10) and the first negative electrode active material layer (22) or due to overcharging of lithium increases. The area of the positive electrode (10) is, for example, equal to the area of the positive electrode active material layer (12). The area of the positive electrode (10) is, for example, equal to the area (11) of the positive electrode current collector.
[0124] The area of the inert member (40) is, for example, 50% or less, 40% or less, 30% or less, 20% or less, or 10% or less of the area of the anode (10). The area of the inert member (40) is, for example, 1% to 50%, 5% to 40%, 5% to 30%, 5% to 20%, or 5% to 15% of the area of the anode (10).
[0125] The area (S1) of the anode (10) is smaller than the area (S4) of the negative electrode current collector (21). The area (S1) of the anode (10) is, for example, less than 100%, 99% or less, 98% or less, 97% or less, 96% or less, or 95% or less of the area (S4) of the negative electrode current collector (21). The area (S1) of the anode (10) is, for example, 50% to less than 100%, 50% to 99%, 55% to 98%, 60% to 97%, 70% to 96%, 80% to 95%, or 85% to 95% of the area (S4) of the negative electrode current collector (21). The area (S4) of the negative electrode current collector (21) is, for example, the same as the area of the negative electrode (20). The area (S4) of the negative electrode current collector (21) is, for example, the same as the area of the first negative electrode active material layer (22).
[0126] In the present disclosure, "identical" area, length, width, thickness, and / or shape includes all cases having "substantially identical" area, length, width, thickness, and / or shape, except where the area, length, width, thickness, and / or shape are intentionally made different from one another. "Identical" area, length, width, and / or thickness includes a range in which the unintended difference in the area, length, width, and / or thickness of the objects being compared is, for example, less than 3%, less than 2%, less than 1%, less than 0.5%, or less than 0.1%.
[0127] The thickness of the inert member (40) is, for example, greater than the thickness of the first cathode active material layer (22). The thickness of the first cathode active material layer (22) is, for example, 50% or less, 40% or less, 30% or less, 20% or less, or 10% or less of the thickness of the inert member (40). The thickness of the first cathode active material layer (22) is, for example, 1% to 50%, 1% to 40%, 1% to 30%, 1% to 20%, or 1% to 10% of the thickness of the inert member (40).
[0128] The inert member (40) may be a gasket. By using a gasket as the inert member (40), cracks in the electrolyte layer (30) caused by pressure differences during the pressurization process can be effectively suppressed.
[0129] The inert member (40) has, for example, a single-layer structure. Alternatively, although not shown in the drawings, the inert member (40) may have a multi-layer structure. In the inert member (40) having a multi-layer structure, each layer may have a different composition. The inert member having a multi-layer structure may have, for example, a two-layer structure, a three-layer structure, a four-layer structure, or a five-layer structure. The inert member (40) having a multi-layer structure may include, for example, one or more adhesive layers and one or more support layers. The adhesive layer effectively prevents separation between the anode (10) and the electrolyte layer (30) caused by volume changes of the anode (10) during the charging and discharging process of the all-solid-state secondary battery (10), for example, and improves the film strength of the inert member (40) by providing bonding force between the support layer and other layers. The support layer provides support to the inert member (40), prevents non-uniformity of pressure applied to the electrolyte layer (30) during the pressurization process or the charging / discharging process, and prevents deformation of the shape of the all-solid-state secondary battery (1) being manufactured.
[0130] The inert member (40) is, for example, a flame-retardant inert member. By providing flame retardancy, the flame-retardant inert member can prevent thermal runaway and the possibility of ignition of the all-solid-state secondary battery (1). As a result, the safety of the all-solid-state secondary battery (1) is further improved. By absorbing residual moisture within the all-solid-state secondary battery (1), the flame-retardant inert member prevents the deterioration of the all-solid-state secondary battery (1), thereby improving the lifespan characteristics of the all-solid-state secondary battery (1).
[0131] The flame-retardant inert member comprises, for example, a matrix and a filler. The matrix comprises, for example, a substrate and a reinforcing material. The matrix comprises, for example, a fibrous substrate and a fibrous reinforcing material. By including the substrate, the matrix may have elasticity. Thus, the matrix can effectively accommodate volume changes during the charging and discharging of the all-solid-state secondary battery (1) and can be placed at various locations. The substrate included in the matrix comprises, for example, a first fibrous material. By including the first fibrous material, the matrix can effectively accommodate volume changes of the positive electrode (30) that occur during the charging and discharging process of the all-solid-state secondary battery (1), and can effectively suppress deformation of the inert member (40) caused by volume changes of the positive electrode (30). The first fibrous material is, for example, a material having an aspect ratio of 5 or more, 20 or more, or 50 or more. The first fibrous material is, for example, a material having an aspect ratio of 5 to 1000, 20 to 1000, or 50 to 1000. The first fibrous material is, for example, an insulating material. Since the first fibrous material is an insulating material, it is possible to effectively prevent a short circuit between the positive electrode (30) and the negative electrode (20) caused by lithium dendrites, etc., that occur during the charging and discharging process of the all-solid-state secondary battery (1). The first fibrous material includes, for example, one or more selected from pulp fiber, insulating polymer fiber, and ion-conducting polymer fiber. The strength of the matrix is enhanced by the matrix including a reinforcing material. Therefore, the matrix can prevent excessive volume change during the charging and discharging of the all-solid-state secondary battery (1) and prevent deformation of the all-solid-state secondary battery. The reinforcing material included in the matrix includes, for example, a second fibrous material. By the reinforcing material including the second fibrous material, the strength of the matrix can be increased more uniformly. The second fibrous material is, for example, a material with an aspect ratio of 3 or more, 5 or more, or 10 or more.The first fibrous material is, for example, a material with an aspect ratio of 3 to 100, 5 to 100, or 10 to 100. The second fibrous material is, for example, a flame-retardant material. Since the second fibrous material is a flame-retardant material, ignition caused by thermal runaway occurring during the charging and discharging process of the all-solid-state secondary battery (1) or due to external impact can be effectively suppressed. The second fibrous material is, for example, glass fiber, metal oxide fiber, ceramic fiber, etc.
[0132] The flame-retardant inert member includes a filler in addition to the matrix. The filler may be placed inside the matrix, on the surface of the matrix, or on both the inside and the surface. The filler is, for example, an inorganic material. The filler included in the flame-retardant inert member is, for example, a moisture getter. The filler prevents the deterioration of the all-solid-state secondary battery (1) by removing residual moisture within the all-solid-state secondary battery (1) by adsorbing moisture at, for example, a temperature below 100°C. Additionally, if the temperature of the all-solid-state secondary battery (1) increases to 150°C or higher due to thermal runaway caused by the charging and discharging process of the all-solid-state secondary battery (1) or external impact, the filler can effectively suppress the ignition of the all-solid-state secondary battery (1) by releasing the adsorbed moisture. That is, the filler is, for example, a flame retardant. The filler is, for example, a metal hydroxide having moisture adsorption properties. The metal hydroxide included in the filler is, for example, Mg(OH)2, Fe(OH)3, Sb(OH)3, Sn(OH)4, TI(OH)3, Zr(OH)4, Al(OH)3, or a combination thereof. The content of the filler included in the flame-retardant inert member is, for example, 10 to 80 parts by weight, 20 to 80 parts by weight, 30 to 80 parts by weight, 40 to 80 parts by weight, 50 to 80 parts by weight, 60 to 80 parts by weight, or 65 to 80 parts by weight, based on 100 parts by weight of the flame-retardant inert member (4).
[0133] The flame-retardant inert member may further include, for example, a binder. The binder may include, for example, a curable polymer or a non-curable polymer. A curable polymer is a polymer that is cured by heat and / or pressure. A curable polymer is, for example, a solid at room temperature. The flame-retardant inert member (40) includes, for example, a heat-pressure curable film and / or a cured product thereof. A heat-pressure curable polymer is, for example, Toray's TSA-66.
[0134] The flame-retardant inert material may additionally include other materials in addition to the substrate, reinforcing material, filler, and binder described above. The flame-retardant inert material may further include one or more materials selected from, for example, paper, insulating polymers, ion-conducting polymers, insulating inorganic materials, oxide-based solid electrolytes, and sulfide-based solid electrolytes. The insulating polymer may be an olefin-based polymer, for example, polypropylene (PP) or polyethylene (PE).
[0135] The density of the substrate or the density of the reinforcing material included in the flame-retardant inert member may be, for example, 10% to 300%, 10% to 150%, 10% to 140%, 10% to 130%, or 10% to 120% of the density of the anode active material included in the anode active material layer (12).
[0136] The inert member (40) is a member that does not contain a material having electrochemical activity, such as an electrode active material. The electrode active material is a material that absorbs / releases lithium. The inert member (40) is a member made of a material other than the electrode active material, such as a material used in the relevant technical field.
[0137] [All-solid-state secondary battery]
[0138] A solid-state secondary battery according to one embodiment comprises the anode described above; a cathode; and an electrolyte layer disposed between the anode and the cathode. The cathode comprises a cathode current collector and a first cathode active material layer disposed on one surface of the cathode current collector.
[0139] Referring to FIGS. 3 to 7, the all-solid-state secondary battery (1) comprises a positive electrode (10); a negative electrode (20); and an electrolyte layer (30) disposed between the positive electrode (10) and the negative electrode (20). The negative electrode (20) comprises a negative electrode current collector (21) and a first negative electrode active material layer (22) disposed on one side of the negative electrode current collector.
[0140] [anode]
[0141] Refer to the anode described above.
[0142] [cathode]
[0143] [Cathode: Cathode active material]
[0144] Referring to FIGS. 3 to 7, the cathode (20) includes a first cathode active material layer (22). The first cathode active material layer (22) includes, for example, a cathode active material and a binder.
[0145] The cathode active material included in the first cathode active layer (22) is a cathode material that can form an alloy or compound with, for example, lithium.
[0146] The negative electrode active material included in the first negative electrode active material layer (22) has, for example, a particle shape. The average particle size of the negative electrode active material having a particle shape is, for example, 4 μm or less, 3 μm or less, 2 μm or less, 1 μm or less, 500 nm or less, 300 nm or less, or 100 nm or less. The average particle size of the negative electrode active material having a particle shape is, for example, 10 nm to 4 μm, 10 nm to 3 μm, 10 nm to 2 μm, 10 nm to 1 μm, 10 nm to 500 nm, 10 nm to 300 nm, or 10 nm to 100 nm. By having the negative electrode active material have an average particle size within this range, reversible absorption and / or desorption of lithium during charging and discharging may be more easily facilitated. The average particle size of the cathode active material is, for example, the median diameter (D50) measured using a laser particle size distribution meter.
[0147] The cathode active material included in the first cathode active material layer (22) comprises, for example, one or more selected from carbon-based cathode active materials and metal or metalloid cathode active materials.
[0148] Carbon-based cathode active materials include, for example, amorphous carbon, crystalline carbon, porous carbon, or a combination thereof.
[0149] The carbon-based cathode active material is, in particular, amorphous carbon. Amorphous carbon is, for example, carbon black (CB), acetylene black (AB), furnace black (FB), ketjen black (KB), graphene, etc., but is not necessarily limited to these, and any material classified as amorphous carbon in the relevant technical field is acceptable. Amorphous carbon is carbon that does not have crystallinity or has very low crystallinity, and is distinguished from crystalline carbon or graphite-based carbon.
[0150] The carbon-based cathode active material may be, for example, porous carbon. The pore volume contained in the porous carbon is, for example, 0.1 cc / g to 10.0 cc / g, 0.5 cc / g to 5 cc / g, or 0.1 cc / g to 1 cc / g. The average pore diameter contained in the porous carbon is, for example, 1 nm to 50 nm, 1 nm to 30 nm, or 1 nm to 10 nm. The BET specific surface area of the porous carbon is, for example, 100 m² 2 / g to 3000 m 2 / g is.
[0151] The metal or metalloid cathode active material comprises one or more selected from the group consisting of gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), and zinc (Zn), but is not necessarily limited to these; any metal cathode active material or metalloid cathode active material that forms an alloy or compound with lithium in the relevant technical field is acceptable. For example, nickel (Ni) is not a metal cathode active material because it does not form an alloy with lithium.
[0152] The first negative electrode active material layer (22) may include a type of negative electrode active material among these negative electrode active materials, or may include a mixture of multiple different negative electrode active materials. For example, the first negative electrode active material layer (22) may include only amorphous carbon, or one or more selected from the group consisting of gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), and zinc (Zn). Alternatively, the first negative electrode active material layer (22) may include a mixture of amorphous carbon and one or more selected from the group consisting of gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), and zinc (Zn). The mixing ratio of a mixture of amorphous carbon and gold, etc., is, for example, 99:1 to 1:99, 10:1 to 1:2, 5:1 to 1:1, or 4:1 to 2:1 by weight ratio, but is not necessarily limited to these ranges and is selected according to the required characteristics of the all-solid-state secondary battery (1). By having the negative electrode active material have this composition, the cycle characteristics of the all-solid-state secondary battery (1) are further improved.
[0153] The negative electrode active material included in the first negative electrode active material layer (22) comprises a mixture of first particles made of, for example, amorphous carbon and second particles made of a metal or metalloid. The metal or metalloid includes, for example, gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), and zinc (Zn). Alternatively, the metalloid is a semiconductor. The content of the second particles is 1 to 99 weight%, 1 to 60 weight%, 8 to 60 weight%, 10 to 50 weight%, 15 to 40 weight%, or 20 to 30 weight% based on the total weight of the mixture. By having the second particles in this range, the cycle characteristics of, for example, the all-solid-state secondary battery (1) are further improved.
[0154] Alternatively, the first negative electrode active material layer (22) comprises a composite negative electrode active material. The composite negative electrode active material may include, for example, a carbon-based support and a metal-based negative electrode active material supported on the carbon-based support. By having such a structure, localization of the metal-based negative electrode active material within the first negative electrode active material layer is prevented, and a uniform distribution can be obtained. Consequently, the cycle characteristics of the all-solid-state secondary battery (1) comprising the first negative electrode active material layer (22) are further improved.
[0155] A metal-based cathode active material supported on a carbon-based support comprises, for example, a metal, a metal oxide, a composite of a metal and a metal oxide, or a combination thereof. The metal includes, for example, gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), tellurium (Te), and zinc (Zn). The metal oxide includes, for example, gold (Au) oxide, platinum (Pt) oxide, palladium (Pd) oxide, silicon (Si) oxide, silver (Ag) oxide, aluminum (Al) oxide, bismuth (Bi) oxide, tin (Sn) oxide, tellurium (Te) oxide, and zinc (Zn) oxide. The metal oxide is, for example, Au x O y (0 <x≤2, 0<y≤3), Pt x O y (0 <x≤1, 0<y≤2), Pd x O y (0 <x≤1, 0<y≤1), Si x O y (0 <x≤1, 0<y≤2), Ag x O y (0 <x≤2, 0<y≤1), Al x O y (0 <x≤2, 0<y≤3), Bi x O y (0 <x≤2, 0<y≤3), Sn x O y (0 <x≤1, 0<y≤2), Te x O y(0 <x≤1, 0<y≤3), Zn x The y (0 <x≤1, 0<y≤1) 또는 이들의 조합을 포함할 수 있다. 금속과 금속산화물의 복합체는 예를 들어 Au와 Au x The y (0 <x≤2, 0<y≤3)의 복합체, Pt와 Pt x The y (0 <x≤1, 0<y≤2)의 복합체, Pd와 Pd x The y (0 <x≤1, 0<y≤1)의 복합체, Si와 Si x The y (0 <x≤1, 0<y≤2)의 복합체, Ag 와 Ag x The y (0 <x≤2, 0<y≤1)의 복합체, Al과 Al x The y (0 <x≤2, 0<y≤3)의 복합체, Bi와 Bi x The y (0 <x≤2, 0<y≤3)의 복합체, Sn과 Sn x The y (0 <x≤1, 0<y≤2)의 복합체, Te과 Te x The y (0 <x≤1, 0<y≤3), Zn과 Zn x The y (0 <x≤1, 0<y≤1)의 복합체, 또는 이들의 조합을 포함할 수 있다.
[0156] The carbon-based support is, for example, amorphous carbon. Amorphous carbon includes, for example, carbon black (CB), acetylene black (AB), furnace black (FB), Kettjen black (KB), graphene, activated carbon, carbon nanofibers (CNF), carbon nanotubes (CNT), etc., but is not necessarily limited to these; any material classified as amorphous carbon in the relevant technical field is acceptable. Amorphous carbon is carbon that does not possess crystallinity or has very low crystallinity, and is distinguished from crystalline carbon or graphite-based carbon. The carbonaceous material is, for example, a carbon-based negative electrode active material.
[0157] The composite cathode active material has, for example, a particle form. The particle size of the composite cathode active material having a particle form is, for example, 10 nm to 4 µm, 10 nm to 1 µm, 10 nm to 500 nm, 10 nm to 200 nm, or 10 nm to 100 nm. Since the composite cathode active material has a particle size within this range, the reversible absorption and / or desorption of lithium during charging and discharging may be more facilitated. The metal-based cathode active material supported on the support may have, for example, a particle form. The particle size of the metal-based cathode active material may be, for example, 1 nm to 200 nm, 1 nm to 150 nm, 5 nm to 100 nm, or 10 nm to 50 nm. The carbon-based support may have, for example, a particle form. The particle size of the carbon-based support may be, for example, 10 nm to 2 µm, 10 nm to 1 µm, 10 nm to 500 nm, 10 nm to 200 nm, or 10 nm to 100 nm. By having a particle size within this range, the carbon-based support can be distributed more uniformly within the first negative electrode active material layer. The carbon-based support may be, for example, nanoparticles with a particle size of 500 nm or less. The particle size of the composite negative electrode active material, the particle size of the metal-based negative electrode active material, and the particle size of the carbon-based support are, for example, average particle sizes. The average particle size is, for example, the median diameter (D50) measured using a laser particle size distribution meter. Alternatively, the average particle size may be determined automatically using software from, for example, electron microscope images, or manually by manual.
[0158] [Cathode: Binder]
[0159] The binder included in the first negative electrode active material layer (22) may be, for example, styrene-butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, vinylidene fluoride / hexafluoropropylene copolymer, polyacrylonitrile, polymethyl methacrylate, etc., but is not necessarily limited to these and any binder used in the relevant technical field is possible. The binder may be composed of a single binder or a plurality of different binders.
[0160] The first negative active material layer (22) is stabilized on the negative current collector (21) by including a binder. Additionally, cracking of the first negative active material layer (22) is suppressed despite changes in volume and / or relative position of the first negative active material layer (22) during the charging and discharging process. For example, if the first negative active material layer (22) does not include a binder, it is possible for the first negative active material layer (22) to be easily separated from the negative current collector (21). As the first negative active material layer (22) is separated from the negative current collector (21), the possibility of a short circuit occurring increases in the portion of the negative current collector (21) that is exposed due to the first negative active material layer (22) coming into contact with the electrolyte layer (30). The first negative electrode active material layer (22) is manufactured by, for example, applying a slurry in which the material constituting the first negative electrode active material layer (22) is dispersed onto a negative electrode current collector (21) and drying it. By including a binder in the first negative electrode active material layer (22), stable dispersion of the negative electrode active material in the slurry is possible. For example, when applying the slurry onto the negative electrode current collector (21) using a screen printing method, it is possible to suppress clogging of the screen (for example, clogging caused by aggregates of the negative electrode active material).
[0161] [Cathode: Other Additives]
[0162] The first negative electrode active material layer (22) may further include additives used in conventional all-solid-state secondary batteries (1), such as fillers, coating agents, dispersants, ion-conducting aids, etc.
[0163] [Cathode: Solid Electrolyte]
[0164] The first negative electrode active material layer (22) may further include a solid electrolyte. The solid electrolyte may be a material selected from, for example, the solid electrolyte included in the electrolyte layer (30). The solid electrolyte included in the first negative electrode active material layer (22) may act as a reaction site where the formation of lithium metal begins within the first negative electrode active material layer (22), act as a space where the formed lithium metal is stored, or act as a path for transmitting lithium ions. The solid electrolyte may be omitted.
[0165] In the first negative electrode active material layer (22), the content of the solid electrolyte may be high in the region adjacent to the electrolyte layer (30), for example, and low in the region adjacent to the negative electrode current collector (21). In the first negative electrode active material layer (22), the solid electrolyte may have a concentration gradient in which the concentration decreases from, for example, the region adjacent to the electrolyte layer (30) to the region adjacent to the negative electrode current collector (21).
[0166] [Cathode: First cathode active material layer]
[0167] The ratio (B / A) of the initial charge capacity (B) of the first negative electrode active material layer (22) and the initial charge capacity (A) of the positive electrode active material layer is 0.005 to 0.45. The initial charge capacity of the positive electrode active material layer (12) is the first open circuit voltage (1 st From open circuit voltage) Li / Li + The initial charging capacity of the first negative electrode active material layer (22) is determined at the maximum charging voltage. nd From open circuit voltage) Li / Li + It is determined at 0.01 V for.
[0168] The maximum charging voltage is determined by the type of cathode active material. The maximum charging voltage can be, for example, 1.5 V, 2.0 V, 2.5 V, 3.0 V, 3.5 V, 4.0 V, 4.2 V, or 4.3 V. For example, the maximum charging voltage of Li2S or Li2S composites is Li / Li + It can be 2.5 V. For example, the maximum charging voltage of Li2S or Li2S composites is Li / Li + The V may be 3.0 V. The ratio (B / A) of the initial charge capacity (B) of the first negative active material layer (22) and the initial charge capacity (A) of the positive active material layer is, for example, 0.01 to 0.3, 0.01 to 0.2, or 0.05 to 0.1. The initial charge capacity (mAh) of the positive active material layer (12) is obtained by multiplying the charge specific capacity (mAh / g) of the positive active material by the mass (g) of the positive active material in the positive active material layer (12). When multiple types of positive active materials are used, the charge specific capacity × mass value is calculated for each positive active material, and the sum of these values is the initial charge capacity of the positive active material layer (12). The initial charge capacity of the first negative active material layer (22) is also calculated in the same way. The initial charge capacity of the first negative electrode active material layer (22) is obtained by multiplying the charge capacity density (mAh / g) of the negative electrode active material by the mass of the negative electrode active material in the first negative electrode active material layer (22). If multiple types of negative electrode active materials are used, the charge capacity density × mass value is calculated for each negative electrode active material, and the sum of these values is the initial charge capacity of the first negative electrode active material layer (22). The charge capacity densities of the positive electrode active material and the negative electrode active material, respectively, can be measured using an all-solid-state half-cell using lithium metal as the counter electrode. The initial charge capacities of the positive electrode active material layer (12) and the first negative electrode active material layer (22), respectively, are at a constant current density, for example, 0.1 mA / cm² 2This can be directly measured using an all-solid-state half-cell. For the anode, the measurement is taken from the first open-circuit voltage (OCV) to the maximum charging voltage, e.g., 3.0 V (vs. Li / Li). + It can be performed for an operating voltage up to ). For the cathode, the measurement can be performed for an operating voltage from the second open circuit voltage (OCV) down to 0.01 V for the cathode, e.g., lithium metal. For example, an all-solid-state half-electrode having a positive electrode active material layer 0.1 mA / cm² from the first open circuit voltage up to 3.0 V. 2 The all-solid-state half-paper having a first negative electrode active material layer, which is charged with a constant current, has a voltage of 0.1 mA / cm² up to 0.01 V from the second open circuit voltage. 2 It can be charged with a constant current. The current density during constant current charging is, for example, 0.2 mA / cm² 2 , or 0.5 mA / cm 2 It may be possible. An all-solid-state half battery having a positive active material layer may be charged, for example, from a first open-circuit voltage to 2.5 V, 2.0 V, 3.5 V, or 4.0 V. The maximum charging voltage of the positive active material layer may be determined by the maximum voltage of the battery satisfying safety conditions according to JISC8712:2015 of the Japanese Standards Association.
[0169] If the initial charge capacity of the first negative electrode active material layer (22) is excessively small, the thickness of the first negative electrode active material layer (22) becomes very thin, and thus, during repeated charge and discharge processes, lithium dendrites formed between the first negative electrode active material layer (22) and the negative electrode current collector (21) cause the first negative electrode active material layer (22) to collapse, making it difficult to improve the cycle characteristics of the all-solid-state secondary battery (1). If the charge capacity of the first negative electrode active material layer (22) increases excessively, the energy density of the all-solid-state secondary battery (1) decreases, and the internal resistance of the all-solid-state secondary battery (1) caused by the first negative electrode active material layer (22) increases, making it difficult to improve the cycle characteristics of the all-solid-state secondary battery (1).
[0170] The thickness of the first negative electrode active material layer (22) is, for example, 50% or less, 40% or less, 30% or less, 20% or less, 10% or less, or 5% or less of the thickness of the positive electrode active material layer (12). The thickness of the first negative electrode active material layer (22) is, for example, 1 to 50%, 1 to 40%, 1 to 30%, 1 to 20%, 1 to 10%, or 1 to 5% of the thickness of the positive electrode active material layer (12). The thickness of the first negative electrode active material layer (22) is, for example, 1 μm to 20 μm, 2 μm to 15 μm, or 3 μm to 10 μm. If the thickness of the first negative electrode active material layer (22) is excessively thin, lithium dendrites formed between the first negative electrode active material layer (22) and the negative electrode current collector (21) cause the first negative electrode active material layer (22) to collapse, making it difficult to improve the cycle characteristics of the all-solid-state secondary battery (1). If the thickness of the first negative electrode active material layer (22) is excessively increased, the energy density of the all-solid-state secondary battery (1) decreases, and the internal resistance of the all-solid-state secondary battery (1) due to the first negative electrode active material layer (22) increases, making it difficult to improve the cycle characteristics of the all-solid-state secondary battery (1). If the thickness of the first negative electrode active material layer (22) decreases, for example, the initial charge capacity of the first negative electrode active material layer (22) also decreases.
[0171] [Cathode: Second cathode active material layer]
[0172] Referring to FIG. 5, the all-solid-state secondary battery (1) further comprises a second negative electrode active material layer (24) disposed, for example, between a negative electrode current collector (21) and a first negative electrode active material layer (22) after charging. The second negative electrode active material layer (24) is a metal layer comprising lithium or a lithium alloy. The metal layer comprises lithium or a lithium alloy. Therefore, since the second negative electrode active material layer (24) is a metal layer containing lithium, it acts as, for example, a lithium reservoir. The lithium alloy is, for example, Li-Al alloy, Li-Sn alloy, Li-In alloy, Li-Ag alloy, Li-Au alloy, Li-Zn alloy, Li-Ge alloy, Li-Si alloy, etc., but is not limited to these, and any alloy used as a lithium alloy in the relevant technical field is possible. The second negative electrode active material layer (24) may be composed of one of these alloys or lithium, or may be composed of various types of alloys. The second negative electrode active material layer (24) is, for example, a plated layer. The second negative electrode active material layer (24) is, for example, deposited between the first negative electrode active material layer (22) and the negative electrode current collector (21) during the charging process of the all-solid-state secondary battery (1).
[0173] The thickness of the second negative electrode active material layer (24) is not particularly limited, but, for example, 1 μm to 500 μm, 1 μm to 200 μm, 1 μm to 150 μm, 1 μm to 100 μm, or 1 μm to 50 μm. If the thickness of the second negative electrode active material layer (24) is excessively thin, it is difficult for the second negative electrode active material layer (24) to perform the role of a lithium reservoir. If the thickness of the second negative electrode active material layer (24) is excessively thick, the mass and volume of the all-solid-state secondary battery (1) increase, and there is a possibility that the cycle characteristics of the all-solid-state secondary battery (1) may deteriorate.
[0174] Alternatively, in the all-solid-state secondary battery (1), the second negative active material layer (24) may be placed between the negative current collector (21) and the first negative active material layer (22) before assembly of the all-solid-state secondary battery (1), for example. When the second negative active material layer (24) is placed between the negative current collector (21) and the first negative active material layer (22) before assembly of the all-solid-state secondary battery (1), the second negative active material layer (24) acts as a lithium reservoir because it is a metal layer containing lithium. For example, a lithium foil may be placed between the negative current collector (21) and the first negative active material layer (22) before assembly of the all-solid-state secondary battery (1).
[0175] When the second negative electrode active material layer (24) is precipitated by charging after assembly of the all-solid-state secondary battery (1), the energy density of the all-solid-state secondary battery (1) increases because the second negative electrode active material layer (24) is not included during assembly of the all-solid-state secondary battery (1). When charging the all-solid-state secondary battery (1), it is charged in excess of the charging capacity of the first negative electrode active material layer (22). That is, the first negative electrode active material layer (22) is overcharged. At the beginning of charging, lithium is absorbed in the first negative electrode active material layer (22). The negative electrode active material contained in the first negative electrode active material layer (22) forms an alloy or compound with lithium ions that have moved from the positive electrode (10). When charging is performed beyond the capacity of the first negative electrode active material layer (22), lithium is deposited, for example, on the back surface of the first negative electrode active material layer (22), that is, between the negative current collector (21) and the first negative electrode active material layer (22), and a metal layer corresponding to the second negative electrode active material layer (24) is formed by the deposited lithium. The second negative electrode active material layer (24) is a metal layer composed mainly of lithium (i.e., metallic lithium). This result is obtained, for example, by the negative electrode active material included in the first negative electrode active material layer (22) including a material that forms an alloy or compound with lithium. During discharge, the lithium in the first negative electrode active material layer (22) and the second negative electrode active material layer (24), i.e., the metal layer, is ionized and moves toward the positive electrode (10). Therefore, it is possible to use lithium as a negative electrode active material in an all-solid-state secondary battery (1). In addition, since the first negative electrode active material layer (22) covers the second negative electrode active material layer (24), it serves as a protective layer for the second negative electrode active material layer (24), i.e., the metal layer, and at the same time, it performs the role of suppressing the precipitation growth of lithium dendrites. Therefore, it suppresses short circuits and capacity degradation of the all-solid-state secondary battery (1), and consequently improves the cycle characteristics of the all-solid-state secondary battery (1).Additionally, when the second negative electrode active material layer (24) is formed by charging after assembly of the all-solid-state secondary battery (1), the negative electrode (20), that is, the negative electrode current collector (21), the first negative electrode active material layer (22), and the region between them are Li-free regions that do not contain lithium (Li) in the initial state or after complete discharge of the all-solid-state secondary battery (1).
[0176] [Cathode: Cathode current collector]
[0177] The negative electrode current collector (21) is composed of a material that does not react with, for example, lithium, that is, does not form any alloys or compounds. The material constituting the negative electrode current collector (21) may be, for example, copper (Cu), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), and nickel (Ni), but is not necessarily limited to these; any material used as an electrode current collector in the relevant technical field is acceptable. The negative electrode current collector (21) may be composed of one of the metals described above, or may be composed of an alloy or coating material of two or more metals. The negative electrode current collector (21) is, for example, in the form of a plate or foil.
[0178] Referring to FIG. 4, the all-solid-state secondary battery (1) may further include a thin film (23) containing an element capable of forming an alloy with lithium on one side of a negative electrode current collector (21). The thin film (23) is disposed between the negative electrode current collector (21) and the first negative electrode active material layer (22). The thin film (23) contains, for example, an element capable of forming an alloy with lithium. The element capable of forming an alloy with lithium is, for example, gold, silver, zinc, tin, indium, silicon, aluminum, bismuth, etc., but is not necessarily limited to these, and any element capable of forming an alloy with lithium in the relevant technical field is possible. The thin film (23) is composed of one of these metals or is composed of an alloy of various types of metals. By placing the thin film (23) on one side of the negative electrode current collector (21), the deposition shape of the second negative electrode active material layer (24) deposited between, for example, the thin film (23) and the first negative electrode active material layer (22) is further flattened, and the cycle characteristics of the all-solid-state secondary battery (1) can be further improved.
[0179] The thickness of the thin film (23) is, for example, 1 nm to 800 nm, 10 nm to 700 nm, 50 nm to 600 nm, or 100 nm to 500 nm. If the thickness of the thin film (23) is less than 1 nm, it may be difficult to perform the function of the thin film (23). If the thickness of the thin film (23) is excessively thick, the thin film (23) itself absorbs lithium, and the amount of lithium precipitated at the negative electrode decreases, which lowers the energy density of the all-solid-state battery and may degrade the cycle characteristics of the all-solid-state secondary battery (1). The thin film (23) may be placed on the negative electrode current collector (21) by, for example, vacuum deposition, sputtering, plating, etc., but is not necessarily limited to these methods, and any method capable of forming the thin film (23) in the relevant technical field is possible.
[0180] Although not shown in the drawing, the negative current collector (21) may include, for example, a base film and a metal layer disposed on one or both sides of the base film. The base film may include, for example, a polymer. The polymer may be, for example, a thermoplastic polymer. The polymer may include, for example, polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polybutylene terephthalate (PBT), polyimide (PI), or a combination thereof. The polymer may be an insulating polymer. By including an insulating thermoplastic polymer in the base film, the base film may soften or liquefy upon the occurrence of a short circuit, thereby blocking battery operation and suppressing a sudden increase in current. The metal layer may include, for example, copper (Cu), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), or an alloy thereof. The negative current collector (21) may additionally include a metal piece and / or a lead tab. For more specific details regarding the base film, metal layer, metal chip, and lead tab of the negative electrode current collector (21), refer to the positive electrode current collector (11) described above. By having this structure, the negative electrode current collector (21) can reduce the weight of the negative electrode and, consequently, improve the energy density of the negative electrode and the lithium battery.
[0181] [Electrolyte layer]
[0182] [Electrolyte layer: Electrolyte]
[0183] Referring to FIGS. 3 to 7, the electrolyte layer (30) comprises an electrolyte disposed between the anode (10) and the cathode (20). The electrolyte may include, for example, a solid electrolyte, a gel electrolyte, or a combination thereof.
[0184] Solid electrolytes may include, for example, sulfide-based solid electrolytes, oxide-based solid electrolytes, polymeric solid electrolytes, or combinations thereof.
[0185] Solid electrolytes are, for example, sulfide-based solid electrolytes. Sulfide-based solid electrolytes are, for example, Li2S-P2S5, Li2S-P2S5-LiX, where X is a halogen element, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n , m, n are positive numbers, Z is one of Ge, Zn, or Ga, Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q , p, q are positive numbers, M is one of P, Si, Ge, B, Al, Ga, In, Li 7-x PS 6-x Cl x , 0(x(2, Li 7-x PS 6-x Br x , 0(x(2, and Li 7-x PS 6-x I x, 0(x(2) is one or more selected from. Sulfide-based solid electrolytes are manufactured by processing starting materials, such as Li2S or P2S5, by methods such as melt quenching or mechanical milling. Additionally, heat treatment may be performed after such processing. The solid electrolyte may be amorphous, crystalline, or a mixture thereof. Furthermore, the solid electrolyte may include sulfur (S), phosphorus (P), and lithium (Li) as at least constituent elements among the sulfide-based solid electrolyte materials described above, for example. For example, the solid electrolyte may be a material containing Li2S-P2S5. When using a sulfide-based solid electrolyte material containing Li2S-P2S5 to form the solid electrolyte, the mixed molar ratio of Li2S and P2S5 is, for example, Li2S : P2S5 = 20 : 80 to 90 : 10, 25 : 75 to 90 : 10, 30 : The range is approximately 70 to 70:30, 40:60 to 60:40.
[0186] Sulfide-based solid electrolytes may include, for example, an argyrodite-type solid electrolyte represented by the following chemical formula 1:
[0187] <Chemical Formula 1>
[0188] Li + 12-n-x A n+ X 2- 6-x Y - x
[0189] In the above formula, A is P, As, Ge, Ga, Sb, Si, Sn, Al, In, Ti, V, Nb, or Ta; X is S, Se, or Te; Y is Cl, Br, I, F, CN, OCN, SCN, or N3; and 1(n(5) and 0(x(2). Sulfide-based solid electrolytes are, for example, Li 7-x PS 6-x Cl x , 0≤x≤2, Li 7-xPS 6-x Br x , 0≤x≤2, and Li 7-x PS 6-x I x It may be an argyrodite-type compound containing one or more selected from 0≤x≤2. The sulfide-based solid electrolyte may be an argyrodite-type compound containing, for example, one or more selected from Li6PS5Cl, Li6PS5Br, and Li6PS5I.
[0190] The density of the argyrodite-type solid electrolyte may be 1.5 to 2.0 g / cc. Since the argyrodite-type solid electrolyte has a density of 1.5 g / cc or higher, the internal resistance of the all-solid-state secondary battery is reduced, and penetration of the electrolyte layer by Li can be effectively suppressed.
[0191] Oxide-based solid electrolytes are, for example, Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 (0 <x<2, 0≤y<3), BaTiO3, Pb(Zr,Ti)O3(PZT), Pb 1-x La x Zr 1-y Ti y O3(PLZT)(0≤x<1, 0≤y<1), PB(Mg3Nb 2 / 3 )O3-PbTiO3(PMN-PT), HfO2, SrTiO3, SnO2, CeO2, Na2O, MgO, NiO, CaO, BaO, ZnO, ZrO2, Y2O3, Al2O3, TiO2, SiO2, Li3PO4, Li x Ti y (PO4)3(0 <x<2, 0<y<3), Li x Al y Ti z (PO4)3(0 <x<2, 0<y<1, 0<z<3), Li1+x+y (Al, Ga) x (Ti, Ge) 2-x Si y P 3-y O 12 (0≤x≤1 0≤y≤1), Li x La y TiO3(0 <x<2, 0<y<3), Li2O, LiOH, Li2CO3, LiAlO2, Li2O-Al2O3-SiO2-P2O5-TiO2-GeO2, Li 3+x La3M2O 12 (M = Te, Nb, or Zr, 0≤x≤10), or a combination thereof. Oxide-based solid electrolytes are produced, for example, by sintering.
[0192] Oxide-based solid electrolytes are, for example, Li7La3Zr2O 12 (LLZO) and Li 3+x La3Zr 2-a M a O 12 (M-doped LLZO, M=Ga, W, Nb, Ta, or Al, 0 <a<2, 0≤x≤10) 중에서 선택된 가넷계(Garnet-type) 고체전해질이다.
[0193] The polymer solid electrolyte may, for example, comprise a mixture of a lithium salt and a polymer, or comprise a polymer having ion-conducting functional groups. The polymer solid electrolyte may, for example, be a polymer electrolyte that is in a solid state at 25 °C and 1 atm. The polymer solid electrolyte may, for example, not contain a liquid.The polymeric solid electrolyte comprises a polymer, wherein the polymer is, for example, polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyethylene oxide (PEO), poly(styrene-b-ethylene oxide) block copolymer (PS-PEO), poly(styrene-butadiene), poly(styrene-isoprene-styrene), poly(styrene-b-divinylbenzene) block copolymer, poly(styrene-ethylene oxide-styrene) block copolymer, polystyrene sulfonate (PSS), polyvinyl fluoride (PVF), poly(methylmethacrylate) (PMMA), polyethylene glycol (PEG), polyacrylonitrile (PAN), polytetrafluoroethylene (PTFE), polyethylenedioxythiophene (PEDOT), polypyrrole (PPY), polyacrylonitrile (PAN). Polyaniline, Polyacetylene, Nafion, Aquivion, Flemion, Gore, Aciplex, Morgane ADP, Sulfonated poly(ether ether ketone) (SPEEK), Sulfonated poly(arylene ether ketone ketone sulfone) (SPAEKKS), Sulfonated poly(aryl ether ketone) (SPAEK), Poly[bis(benzimidazobenzisoquinolinones)] (SPBIBI), Poly(styrene sulfonate) (PSS), Lithium 9,10-Diphenylanthracene-2-sulfonate (lithium 9,10-diphenylanthracene-2-sulfonate, DPASLi. +It may be ) or a combination thereof, but is not limited thereto, and any that are used in polymer electrolytes in the relevant technical field are permitted. Any lithium salt that can be used as a lithium salt in the relevant technical field is permitted. Examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, LiAlO2, LiAlCl4, LiN(C x F 2x+1 SO2)(C y F 2y+1 The polymer may be SO2)(x and y are each 1 to 20), LiCl, LiI, or a mixture thereof. The polymer included in the polymer solid electrolyte may be, for example, a compound containing 10 or more, 20 or more, 50 or more, or 100 or more repeating units. The weight-average molecular weight of the polymer included in the polymer solid electrolyte may be, for example, 1,000 Dalton or more, 10,000 Dalton or more, 100,000 Dalton or more, or 1,000,000 Dalton or more.
[0194] Gel electrolytes are, for example, polymeric gel electrolytes. Gel electrolytes can have a gel state without, for example, containing polymers.
[0195] Polymer gel electrolytes may, for example, comprise a liquid electrolyte and a polymer, or comprise an organic solvent and a polymer having ion-conducting functional groups. Polymer gel electrolytes may, for example, be polymer electrolytes in a gel state at 25 °C and 1 atm. Polymer gel electrolytes may, for example, have a gel state without containing a liquid. The liquid electrolyte used in the polymer gel electrolyte may be, for example, an ionic liquid, a mixture of a lithium salt and an organic solvent; a mixture of a lithium salt and an organic solvent; a mixture of an ionic liquid and an organic solvent; or a mixture of a lithium salt, an ionic liquid, and an organic solvent. The polymer used in the polymer gel electrolyte may be selected from polymers used in solid polymer electrolytes. The organic solvent may be selected from organic solvents used in liquid electrolytes. The lithium salt may be selected from lithium salts used in solid polymer electrolytes. An ionic liquid refers to a salt or a room-temperature molten salt that has a melting point below room temperature, consists solely of ions, and is in a liquid state at room temperature. The ionic liquid may include, for example, one or more compounds selected from a) one or more cations selected from ammonium-based, pyrrolidinium-based, pyridinium-based, pyrimidinium-based, imidazolium-based, piperidinium-based, pyrazolium-based, oxazolium-based, pyridazinium-based, phosphonium-based, sulfonium-based, triazolium-based, and mixtures thereof, and b) one or more anions selected from BF4-, PF6-, AsF6-, SbF6-, AlCl4-, HSO4-, ClO4-, CH3SO3-, CF3CO2-, Cl-, Br-, I-, BF4-, SO4-, CF3SO3-, (FSO2)2N-, (C2F5SO2)2N-, (C2F5SO2)(CF3SO2)N-, and (CF3SO2)2N-. A polymer solid electrolyte can form a polymer gel electrolyte by impregnating it into a liquid electrolyte, for example, in a secondary battery. The polymer gel electrolyte may further include inorganic particles.The polymer included in the polymer gel electrolyte may be, for example, a compound containing 10 or more, 20 or more, 50 or more, or 100 or more repeating units. The weight-average molecular weight of the polymer included in the polymer gel electrolyte may be, for example, 500 Dalton or more, 1000 Dalton or more, 10,000 Dalton or more, 100,000 Dalton or more, or 1,000,000 Dalton or more.
[0196] [Electrolyte layer: Binder]
[0197] The electrolyte layer (30) may include, for example, a binder. The binder included in the electrolyte layer (30) may be, for example, styrene-butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, etc., but is not limited to these and any binder used in the relevant technical field is possible. The binder of the electrolyte layer (30) may be the same as or different from the binder included in the positive electrode active material layer (12) and the negative electrode active material layer (22). The binder may be omitted.
[0198] The binder content included in the electrolyte layer (30) is 0.1 to 10 wt%, 0.1 to 5 wt%, 0.1 to 3 wt%, 0.1 to 1 wt%, 0 to 0.5 wt%, or 0 to 0.1 wt% with respect to the total weight of the electrolyte layer (30).
[0199] The creative idea is explained in more detail through the following examples and comparative examples. However, the examples are intended to illustrate the creative idea and do not limit the scope of the creative idea to these examples alone.
[0200] (Manufacturing of composite cathode active material)
[0201] Example 1: Li2S-LiI-CNF, 2 stages, 10 hr, 600 rpm, 28G
[0202] (Stage 1)
[0203] Li2S and LiI were mixed in a weight ratio of 30:20. The mixture was mechanically milled using a ball mill to prepare a Li2S-LiI composite. The milling conditions were 25 ℃ and 600 rpm for 10 hours. The milling energy applied to the sample during milling was 28 G.
[0204] (Stage 2)
[0205] A Li2S-LiI composite and carbon nanofiber (CNF) were mixed in a weight ratio of 50:10. The mixture was mechanically milled using a ball mill to prepare a Li2S-LiI-CNF composite. The milling conditions were 25 ℃ and 600 rpm for 10 hours. The milling energy applied to the sample during milling was 28 G. The Li2S-LiI-CNF composite was used as a composite cathode active material.
[0206] The Mohs hardness of Li2S was 0.6, the Mohs hardness of LiI was 2.0, and the Mohs hardness of carbon nanofiber (CNF) was 1.5.
[0207] Example 2: Li2S-LiI-CNF, 2 steps, 8 hr, 600 rpm, 28G
[0208] A Li2S-LiI-CNF composite was prepared in the same manner as in Example 1, except that the milling time in the first and second steps was changed to 8 hours.
[0209] Example 3: Li2S-LiI-CNF, 2 steps, 6 hr, 600 rpm, 28G
[0210] A Li2S-LiI-CNF composite was prepared in the same manner as in Example 1, except that the milling time in the first and second steps was changed to 6 hours.
[0211] Example 4: Li2S-LiI-CNF, 2 steps, 4 hr, 600 rpm, 28G
[0212] A Li2S-LiI-CNF composite was prepared in the same manner as in Example 1, except that the milling time in the first and second steps was changed to 4 hours.
[0213] Comparative Example 1: Li2S-LiI-CNF, 2 stages, 1 hr, 600 rpm, 28G
[0214] A Li2S-LiI-CNF composite was prepared in the same manner as in Example 1, except that the milling time in the first and second steps was changed to 1 hour.
[0215] Comparative Example 2: Li2S-LiI-CNF, 2 stages, 20 hr, 600 rpm, 28G
[0216] A Li2S-LiI-CNF composite was prepared in the same manner as in Example 1, except that the milling time in the first and second steps was changed to 20 hours.
[0217] Comparative Example 3: Li2S-LiI-CNF, 510 rpm, 10 hr, 2 stages, 20G (KR 2017-0068448 (Tatsumisago), conditions of Example 2 (Li2S-LiI-CNF))
[0218] (Stage 1)
[0219] A first mixture was prepared by mixing Li2S and LiI in a weight ratio of 30:20. A Li2S-LiI composite was prepared by mechanically milling the first mixture using a ball mill.
[0220] The milling conditions were 25 ℃ and 510 rpm for 10 hours. The milling energy applied to the sample during milling was 20 G.
[0221] (Stage 2)
[0222] A second mixture was prepared by mixing a Li2S-LiI composite and carbon nanofiber (CNF) in a weight ratio of 50:10. The second mixture was mechanically milled using a ball mill to produce a Li2S-LiI-CNF composite.
[0223] The milling conditions were 25 ℃ and 510 rpm for 10 hours. The milling energy applied to the sample during milling was 20 G. A Li2S-LiI-CNF composite was used as the composite cathode active material.
[0224] Comparative Example 4: Li2S-LiI-CNF, 10 hr, 2 steps, 10 G
[0225] A Li2S-LiI-CNF composite was prepared in the same manner as in Example 1, except that the rotational speed was reduced in the first and second steps and the milling energy was changed to 10 G.
[0226] Comparative Example 5: Li2S-LiI-CNF, 10 hr, 2 steps, 30 G
[0227] A Li2S-LiI-CNF composite was prepared in the same manner as in Example 1, except that the milling energy was changed to 30 G by increasing the rotational speed in the first and second steps.
[0228] Comparative Example 6: Simple mixture of Li2S and CNF
[0229] Li2S and carbon nanofiber (CNF) were mixed in a weight ratio of 30:30. The mixture was used as is as an anode active material.
[0230] Comparative Example 7: Li2S-CNF, 600 rpm, 2 hr, Stage 1, 20 G
[0231] Li2S and carbon nanofibers (CNF) were mixed in a weight ratio of 30:30. The mixture was mechanically milled using a ball mill to prepare a Li2S-LiI composite. The milling conditions were 25 ℃ and 600 rpm for 2 hours. The milling energy applied to the sample during milling was 20 G. The Li2S-CNF composite was used as a composite cathode active material.
[0232] Comparative Example 8: Li2S-CNF, 600 rpm, 10 hr, Stage 1, 20 G
[0233] A Li2S-CNF composite was prepared using the same method as Comparative Example 5, except that the milling time was changed to 10 hours.
[0234] Comparative Example 9: Li2S-CNF-LiI, 600 rpm, 10 hr, 2 stages, 20G
[0235] (Stage 1)
[0236] Li2S and carbon nanofibers (CNF) were mixed in a weight ratio of 30:10. The mixture was mechanically milled using a ball mill to prepare a Li2S-CNF composite. The milling conditions were 25 ℃ and 600 rpm for 10 hours. The milling energy applied to the sample during milling was 20 G.
[0237] (Stage 2)
[0238] The Li2S-CNF composite and LiI were mixed in a weight ratio of 40:20. The mixture was mechanically milled using a ball mill to prepare the Li2S-CNF-LiI composite. The milling conditions were 25 ℃ and 600 rpm for 10 hours. The milling energy applied to the sample during milling was 20 G. The Li2S-LiI-CNF composite was used as a composite cathode active material.
[0239] Comparative Example 10: Li2S-SE-CNF, 600 rpm, 10 hr, 2 stages, 20G
[0240] (Stage 1)
[0241] Li2S and Li6PS5Cl solid electrolyte (SE) were mixed in a weight ratio of 30:20. The mixture was mechanically milled using a ball mill to prepare a Li2S-SE composite. The milling conditions were 25 ℃ and 600 rpm for 10 hours. The milling energy applied to the sample during milling was 20 G.
[0242] (Stage 2)
[0243] The Li2S-SE composite and CNF were mixed in a weight ratio of 50:10. The mixture was mechanically milled using a ball mill to prepare the Li2S-SE-CNF composite. The milling conditions were 25 ℃ and 600 rpm for 10 hours. The milling energy applied to the sample during milling was 20 G. The Li2S-SE-CNF composite was used as a composite cathode active material.
[0244] Comparative Example 11: Li2S-LiI-CNF, 600 rpm, 2 hr, 1 stage, 20 G
[0245] Li2S, LiI, and carbon nanofibers (CNF) were mixed in a weight ratio of 30:20:10. The mixture was mechanically milled using a ball mill to prepare a Li2S-LiI-CNF composite. The milling conditions were 25 ℃ and 600 rpm for 2 hours. The milling energy applied to the sample during milling was 20 G. The Li2S-LiI-CNF composite was used as a composite cathode active material.
[0246] (Manufacturing of positive and secondary batteries)
[0247] Example 5
[0248] (Anode manufacturing)
[0249] As the cathode active material, the Li2S-LiI-CNF composite prepared in Example 1 was prepared. As the solid electrolyte, Li6PS5Cl, an argyrodite-type crystal (D50=3.0 μm, crystalline), was prepared. As the binder, PTFE was prepared. These materials were mixed in a weight ratio of composite cathode active material : solid electrolyte : binder = 60 : 40 : 1.2 to prepare a cathode composite. The cathode composite was obtained by dry mixing using a ball mill.
[0250] An anode was manufactured by placing the anode composite on one side of an anode current collector made of aluminum foil coated with carbon on one side and performing a plate press at a pressure of 200 MPa for 10 minutes. The thickness of the anode was approximately 120 μm. The thickness of the anode active material layer was approximately 100 μm, and the thickness of the carbon-coated aluminum foil was approximately 20 μm. The area of the anode active material layer and the anode current collector were the same.
[0251] (Cathode manufacturing)
[0252] A SUS foil with a thickness of 10 μm was prepared as a negative electrode current collector. As negative electrode active materials, carbon black (CB) with a primary particle size of about 30 nm and silver (Ag) particles with an average particle diameter of about 60 nm were prepared.
[0253] 4 g of a mixed powder, prepared by mixing carbon black (CB) and silver (Ag) particles in a weight ratio of 3:1, was placed in a container, and 4 g of an NMP solution containing 7 wt% of a PVDF binder (Kureha # 9300) was added to prepare a mixed solution. A slurry was prepared by stirring the mixed solution while gradually adding NMP to it. The prepared slurry was applied to a SUS sheet using a bar coater, dried in air at 80°C for 10 minutes, and then vacuum dried at 40°C for 10 hours to prepare a laminate. The prepared laminate was cold-roll-pressed to flatten the surface to prepare a cathode having a first cathode active material layer / cathode current collector structure. The thickness of the first cathode active material layer was approximately 15 μm. The area of the first cathode active material layer and the cathode current collector were the same.
[0254] (Preparation of solid electrolyte layer)
[0255] Li6PS5Cl solid electrolyte, an argyrodite-type crystal (D 50 A mixture was prepared by adding 1.5 parts by weight of an acrylic binder to 98.5 parts by weight of a solid electrolyte at a concentration of 3.0 (m, crystalline). A slurry was prepared by stirring while adding octyl acetate to the prepared mixture. The prepared slurry was applied using a bar coater onto a 15 μm thick nonwoven fabric placed on a 75 μm thick PET substrate, and a laminate was prepared by drying in air at a temperature of 80 °C for 10 minutes. A solid electrolyte layer was prepared by vacuum drying the prepared laminate at 80 °C for 2 hours.
[0256] (Inert component)
[0257] A flame-retardant inert member was manufactured by mixing cellulose fiber, glass fiber, aluminum hydroxide (Al(OH)3), an acrylic binder, and a solvent, forming the mixture into a gasket shape, and then removing the solvent.
[0258] The weight ratio of cellulose fiber, glass fiber, aluminum hydroxide (Al(OH)3), and acrylic binder was 20:8:70:2. The thickness of the inert material was 120 μm.
[0259] Before placing the manufactured flame-retardant inert material on the solid electrolyte layer, vacuum heat treatment was performed at 80°C for 5 hours to remove moisture, etc. from the flame-retardant inert material.
[0260] (Manufacturing of all-solid-state secondary batteries)
[0261] Referring to FIG. 3, a solid electrolyte layer was placed on the cathode such that a first cathode active material layer contacted the solid electrolyte layer, and an anode was placed on the solid electrolyte layer. A laminate was prepared by placing a gasket around the anode and in contact with the solid electrolyte layer. The thickness of the gasket was approximately 120 μm. The flame-retardant inert material was used as the gasket. The gasket was placed so as to contact the side of the anode and the solid electrolyte layer. The anode was placed in the center of the solid electrolyte layer, and the gasket was placed surrounding the anode and extending to the end of the solid electrolyte layer. The area of the anode was approximately 90% of the area of the solid electrolyte layer, and the gasket was placed over the entire remaining 10% of the area of the solid electrolyte layer where the anode was not placed.
[0262] The prepared laminate is 85 oPlate press treatment was performed at a pressure of 500 MPa for 30 min at C. This pressurization treatment sintered the solid electrolyte layer, thereby improving battery characteristics. The thickness of the sintered solid electrolyte layer was approximately 45 μm. The density of the Li6PS5Cl solid electrolyte, an argyrodite-type crystal contained in the sintered solid electrolyte layer, was 1.6 g / cc. The area of the solid electrolyte layer was equal to the area of the negative electrode.
[0263] An all-solid-state secondary battery was manufactured by placing a pressurized laminate into a pouch and vacuum sealing it. Parts of the positive and negative current collectors were extended outside the sealed battery to be used as the positive and negative terminals.
[0264] Examples 6 to 8
[0265] A cathode and an all-solid-state secondary battery were manufactured in the same manner as in Example 5, except that the composite cathode active materials prepared in Examples 2 to 4 were each used.
[0266] Comparative Examples 12 to 22
[0267] A cathode and an all-solid-state secondary battery were prepared in the same manner as in Example 5, except that the composite cathode active materials prepared in Comparative Examples 1 to 11 were each used.
[0268] Evaluation Example 1: XRD Analysis and Scanning Electron Microscopy Analysis
[0269] XRD spectra were measured using Cu Kα radiation for the bare Li2S used in Example 1, ground Li2S, the Li2S-LiI composite prepared in the first step of Example 1, and the Li2S-LiI-CNF composite prepared in Example 1. The measurement results are shown in Table 1 and Figure 1 below. The Li2S crystallite size and lattice constant were derived from the first peak corresponding to the (111) crystal plane appearing at the diffraction angle 2θ = 27° ± 2.0° in the XRD spectrum.
[0270] The ground Li2S was prepared by milling under the same conditions as in the first step of Example 1, except that the 30:20 weight ratio mixture of Li2S and LiI was changed to 50 parts by weight of Li2S. The second step was not performed.
[0271] The particle size (i.e., D50 particle size) of the composites was measured using a laser particle size analyzer (PSA) and a scanning electron microscope for the raw material Li2S used in Example 1, pulverized Li2S, the Li2S-LiI composite prepared in the first step of Example 1, and the Li2S-LiI-CNF composite prepared in Example 1. The measurement results are shown in Table 1 and Figures 2a and 2b below.
[0272] 2nd peak position [°] Li2S crystallite size [nm] Particle size [㎛] bare Li2S 27.0211 64.67 8 1st peak position [°] Li2S crystallite size [nm] Particle size [㎛] Crushed Li2S 26.9270 15.42 - Li2S-LiI complex (Phase 1) 26.6074 8.83 Less than 1 Example 1 (Li2S-LiI-CNF composite) 26.7020 9.86 Less than 1
[0273] As shown in Table 1, the position of the first peak for the (111) crystal plane appearing at a diffraction angle 2θ = 27° ± 2.0° of the Li2S-LiI-CNF composite of Example 1 shifted to a lower angle compared to the position of the second peak for the (111) crystal plane appearing at a diffraction angle 2θ = 27° ± 2.0° of bare Li2S. The first diffraction angle of the first peak of the Li2S-LiI-CNF composite of Example 1 was smaller than the second diffraction angle of the second peak of bare Li2S. Therefore, the crystallite size of the Li2S-LiI-CNF composite of Example 1 was significantly reduced compared to the crystallite size of bare Li2S.
[0274] As shown in Table 1 and Figure 1, the position of the first peak of the Li2S-LiI-CNF composite of Example 1 and the Li2S-LiI composite, which is the intermediate product of the first step of Example 1, shifted to a lower angle compared to the position of the first peak of the ground Li2S.
[0275] Although not shown in Table 1, the first lattice constant (d1) derived from the first peak for the (111) crystal plane at the diffraction angle 2θ = 27° ± 2.0° of the Li2S-LiI-CNF composite of Example 1 was larger than the second lattice constant (d2) derived from the second peak for the (111) crystal plane at the diffraction angle 2θ = 27° ± 2.0° of bare Li2S. The first lattice constant (d1) was greater than 5.78.
[0276] It was determined that this was due to the increase in the lattice constant value caused by the dissolution of LiI within the Li2S crystal. It was confirmed that the Li2S-LiI-CNF complex forms a solid solution.
[0277] Although not shown in Table 1, the first peak of the Li2S-LiI-CNF composite of Example 1 had a first full width at half maximum (FWHM1), and the second peak of bare Li2S had a second full width at half maximum (FWHM2), and the first full width at half maximum was greater than the second full width at half maximum. The first full width at half maximum (FWHM1) was 1° or greater.
[0278] Evaluation Example 2: XRD Analysis and Scanning Electron Microscopy Analysis
[0279] XRD spectra were measured using Cu Kα radiation for the composite cathode active materials (i.e., composites) prepared in Examples 1 to 4 and Comparative Examples 1 to 11. The Li2S crystallite size calculated from the first peak for the (111) crystal plane appearing at a diffraction angle 2θ = 27° ± 2.0° in the measured XRD spectra is shown in Table 2 below. The crystallite size was calculated using the Sherrer Equation.
[0280] For the composite cathode active materials prepared in Examples 1 to 4 and Comparative Examples 1 to 11, the particle size (D50 particle size) of the composite cathode active materials was measured using a laser particle size analyzer (PSA) and a scanning electron microscope. The measurement results are shown in Table 2 below.
[0281] Stage 1 Milling 2nd stage milling Solid solution formation Li2S crystallite size [nm] Particle size [㎛] Example 1 (28 G, 10 hr) (Li2S-LiI-CNF composite) 600 rpm, 28 G, 10 hr 600 rpm, 28 G, 10 hr ○ 9.8 Less than 1 Example 2 (28 G, 8 hr) (Li2S-LiI-CNF composite) 600 rpm, 28 G, 8 hr 600 rpm, 28 G, 8 hr ○ 7.2 Less than 1 Example 3 (28 G, 6 hr) (Li2S-LiI-CNF composite) 600 rpm, 28 G, 6 hr 600 rpm, 28 G, 6 hr ○ 8.2 Less than 1 Example 4 (28 G, 4 hr) (Li2S-LiI-CNF composite) 600 rpm, 28 G, 4 hr 600 rpm, 28 G, 4 hr ○ 9.5 Less than 1 Comparative Example 1 (28 G, 1 hr) (Li2S-LiI-CNF complex) 600 rpm, 28 G, 1 hr 600 rpm, 28 G, 1 hr ○ 20.1 Less than 1 Comparative Example 2 (28 G, 20 hr) (Li2S-LiI-CNF complex) 600 rpm, 28 G, 20 hr 600 rpm, 28 G, 20 hr △ 11.8 Less than 1 Comparative Example 3 (Li2S-LiI-CNF complex) 510 rpm, 20 G, 10 hr 510 rpm, 20 G, 10 hr ○ 9.9 Less than 1 Comparative Example 4 (7 G, 10 hr) (Li2S-LiI-CNF complex) 300 rpm, 7 G, 10 hr 300 rpm, 7 G, 10 hr × 27.2 3 Comparative Example 5 (38G, 10 hr) (Li2S-LiI-CNF complex) 700 rpm, 38 G, 10 hr 700 rpm, 38 G, 10 hr △ 15.6 2 Comparative Example 6 (0 G) (Li2S + CNF simple mixture) - - × 66.67 8 Comparative Example 7 (28 G, 1 hr) (Li2S-CNF complex) 600 rpm, 20 G, 2 hr - × 24.07 3 Comparative Example 8 (28 G, 10 hr) (Li2S-CNF complex) 600 rpm, 20 G, 10 hr - × 9.89 Less than 1 Comparative Example 9 (28 G, 10 hr) (Li2S-CNF-LiI complex) 600 rpm, 28 G, 10 hr 600 rpm, 28 G, 10 hr × 15.2 2 Comparative Example 10 (28 G, 10 hr) (Li2S-SE-CNF complex) 600 rpm, 28 G, 10 hr 600 rpm, 28 G, 10 hr × 8.9 Less than 1 Comparative Example 11 (28 G, 2 hr) (Li2S-LiI-CNF complex) 600 rpm, 20 G, 2 hr - ○ 22 3
[0282] As shown in Table 2, the Li2S-LiI-CNF composites of Examples 1 to 4 contain a Li2S-LiI solid solution, the size of the Li2S crystallites is less than 9.9 nm, and the composite particle size is 2 μm or less.
[0283] The Li2S-LiI-CNF composite of Comparative Example 1 had a size of Li2S crystallites greater than 9.9 nm as the milling energy was reduced during manufacturing.
[0284] In the Li2S-LiI-CNF composite of Comparative Example 2, as the milling energy increased during manufacturing, LiI phase-separated into a separate phase and failed to form a solid solution, and the size of the Li2S crystallites also increased.
[0285] The Li2S-LiI-CNF composite of Comparative Example 4 failed to form a Li2S-LiI solid solution because the milling energy was excessively reduced during manufacturing.
[0286] In the Li2S-LiI-CNF composite of Comparative Example 5, the Li2S-LiI solid solution was not properly formed due to the heat generated by the increased milling energy during manufacturing.
[0287] The Li2S-LiI-CNF composite of Comparative Example 11 is prepared in the first step, so it contains a Li2S-LiI solid solution, but the Li2S crystallite size increases and the composite particle size exceeds 2 μm.
[0288] The simple mixture of Li2S and CNF of Comparative Example 6, the Li2S-CNF composites of Comparative Examples 5 to 6, and the Li2S-SE-LiI composite of Comparative Example 10 did not form a solid solution.
[0289] In Comparative Example 9, the Li2S-CNF-LiI composite was not properly formed because the Li2S-CNF composite was prepared in the first step and then the Li2S-CNF-LiI composite was prepared in the second step.
[0290] Evaluation Example 3: Charge / Discharge Test
[0291] The charge-discharge characteristics of the all-solid-state secondary batteries of Examples 5 to 8 and Comparative Examples 12 to 22, which employed the composite cathode active materials prepared in Examples 1 to 4 and Comparative Examples 1 to 11, were evaluated by the following charge-discharge test.
[0292] The charge / discharge test was performed by placing the all-solid-state secondary battery in a constant temperature bath at 45°C.
[0293] The first cycle involved charging at a constant current of 0.1 C for 12.5 hours until the battery voltage reached 2.5 V to 2.8 V. Subsequently, discharging was performed at a constant current of 0.1 C for 12.5 hours until the battery voltage reached 0.3 V.
[0294] The discharge capacity of the first cycle was set as the standard capacity. The standard capacity is expressed as the specific capacity of Li2S in Table 1 below.
[0295] After the second cycle, charging and discharging were performed for up to 150 cycles under the same conditions as the first cycle. The measurement results are shown in Table 3 below. The initial efficiency is expressed by the following Equation 1.
[0296] <Mathematical Formula 1>
[0297] Initial efficiency [%] = [1st cycle discharge capacity / 1st cycle charge capacity] × 100
[0298] The number of cycles refers to the number of cycles required for the discharge capacity to decrease to 80% of the standard capacity after the second cycle. It was considered that the life characteristics were superior as the number of cycles increased.
[0299] Stage 1 Milling 2nd stage milling Solid solution formation Capacity [mAh / g] Initial efficiency [%] Cycle count [times] Example 1 (28 G, 10hr) (Li2S-LiI-CNF composite) 600 rpm, 28 G, 10 hr 600 rpm, 28 G, 10 hr ○ 952 91 100 Example 2 (28 G, 8 hr) (Li2S-LiI-CNF composite) 600 rpm, 28 G, 8 hr 600 rpm, 28 G, 8 hr ○ 946 89 250 Example 3 (28 G, 6 hr) (Li2S-LiI-CNF composite) 600 rpm, 28 G, 6 hr 600 rpm, 28 G, 6 hr ○ 948 89.8 200 Example 4 (28 G, 4 hr) (Li2S-LiI-CNF composite) 600 rpm, 28 G, 4 hr 600 rpm, 28 G, 4 hr ○ 950 90 130 Comparative Example 1 (28 G, 1 hr) (Li2S-LiI-CNF complex) 600 rpm, 28 G, 1 hr 600 rpm, 28 G, 1 hr ○ 410 88 85 Comparative Example 2 (28 G, 20 hr) (Li2S-LiI-CNF complex) 600 rpm, 28 G, 20 hr 600 rpm, 28 G, 20 hr △ 650 85.9 78 Comparative Example 3 (Li2S-LiI-CNF complex) 510 rpm, 20 G, 10 hr 510 rpm, 20 G, 10 hr ○ 895 88 92 Comparative Example 4 (7 G, 10 hr) (Li2S-LiI-CNF complex) 300 rpm, 10 G, 10 hr 300 rpm, 10 G, 10 hr × 310 85 50 Comparative Example 5 (38 G, 10 hr) (Li2S-LiI-CNF complex) 700 rpm, 30 G, 10 hr 700 rpm, 30 G, 10 hr △ 350 85 88 Comparative Example 6 (0 G) (Li2S + CNF simple mixture) - - × 30 - - Comparative Example 7 (20 G, 2 hr) (Li2S-CNF complex) 600 rpm, 20 G, 2 hr - × 258 90 - Comparative Example 8 (20 G, 10 hr) (Li2S-CNF complex) 600 rpm, 20 G, 10 hr - × 799 82 2 Comparative Example 9 (20 G, 10 hr) (Li2S-CNF-LiI complex) 600 rpm, 20 G, 10 hr 600 rpm, 20 G, 10 hr × 580 85 50 Comparative Example 10 (20 G, 10 hr) (Li2S-SE-CNF complex) 600 rpm, 20 G, 10 hr 600 rpm, 20 G, 10 hr × 0 - - Comparative Example 11 (20 G, 2 hr) (Li2S-LiI-CNF complex) 600 rpm, 20 G, 2 hr - ○ 250 91 100
[0300] As shown in Table 3, the all-solid-state secondary batteries of Examples 5 to 8 employing the composite cathode active materials of Examples 1 to 4 showed improved discharge capacity, initial efficiency, and lifespan characteristics compared to the all-solid-state secondary batteries of Comparative Examples 12 to 22 employing the composite cathode active materials of Comparative Examples 1 to 11.
[0301] The all-solid-state secondary battery of Comparative Example 12, which used the composite cathode active material of Comparative Example 1 with increased crystallite size, had reduced discharge capacity and lifespan characteristics.
[0302] The all-solid-state secondary battery of Comparative Example 13, which employed the composite cathode active material of Comparative Example 2 containing a separate LiI phase and having an increased crystallite size, also showed reduced discharge capacity and lifespan characteristics. The all-solid-state secondary batteries of Comparative Examples 14 to 15, which employed the composite cathode active materials of Comparative Examples 3 to 4 with increased crystallite size, also showed reduced discharge capacity and lifespan characteristics.
[0303] The all-solid-state secondary battery of Comparative Example 16, which employed the composite cathode active material of Comparative Example 5 containing a separate LiI phase and having increased crystallite size, also showed reduced discharge capacity and lifespan characteristics.
[0304] The all-solid-state secondary batteries of Comparative Examples 17 to 21, which employed the composite cathode active materials of Comparative Examples 6 to 10, showed poor performance in one or more of the discharge capacity and lifespan characteristics.
[0305] The all-solid-state secondary battery of Comparative Example 22, which uses the composite cathode active material of Comparative Example 11 manufactured by performing only one-step milling, has excellent lifespan characteristics but a significantly reduced discharge capacity.
[0306] Although not shown in the drawings, it was confirmed that a lithium metal layer was formed in the second negative electrode active material layer between the first negative electrode active material layer and the negative electrode current collector after initial charging in the all-solid-state secondary batteries of Examples 5 to 8. This was confirmed through cross-sectional scanning electron microscope images of the all-solid-state secondary batteries. Explanation of the symbols
[0307] 1 All-solid-state secondary battery 10 cathode 11 Anode current collector 12 Anode active material layer 20 Cathode 21 Cathode current collector 22 First cathode active material layer 30 Electrolyte layer 40 inert members
Claims
Claim 1 A composite cathode active material comprising a composite of M2S, an alkali metal salt, and a carbon-based material, wherein M is an alkali metal and the alkali metal is Li or Na, the size of the M2S crystallite obtained from the XRD spectrum of the composite is less than 9.9 nm, the composite comprises a solid solution of M2S and an alkali metal salt, the composite comprises one type of alkali metal salt, and the size of the composite particles is 2 μm or less. Claim 2 In claim 1, the alkali metal salt is a lithium salt or a sodium salt, the alkali metal salt is a binary compound or a ternary compound, the binary compound comprises LiI, LiBr, LiCl, LiF, LiH, Li2O, Li2Se, Li2Te, Li3N, Li3P, Li3As, Li3Sb, Li3Al2, or LiB3, or comprises NaI, NaBr, NaCl, NaF, Na2O, Na2Se, Na3N, Na3P, Na3As, Na3Sb, Na3Al2, or NaB3, and the ternary compound comprises Li3OCl, LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiNO3, Li2CO3, LiBH4, Li2SO4, Li3BO3, Li3PO4, Li4NCl, Li5NCl2, A composite cathode active material comprising Li3BN2 or Na3OCl, NaBF4, NaPF6, NaAsF6, NaClO4, NaNO3, NaAlO2, NaAlCl4, NaNO3, Na2CO3, NaBH4, Na2SO4, Na3BO3, Na3PO4, Na4NCl, Na5NCl2, or Na3BN2. Claim 3 A composite cathode active material according to claim 1, wherein the molar ratio of M2S to alkali metal salt in the composite is 50:50 to 95:
5. Claim 4 A composite cathode active material according to claim 1, wherein the first lattice constant (d1) derived from the first peak appearing at the diffraction angle 2θ = 27° ± 2.0° corresponding to the (111) crystal plane of M2S in the XRD spectrum of the composite is larger than the second lattice constant (d2) derived from the second peak appearing at the diffraction angle 2θ = 27° ± 2.0° corresponding to the (111) crystal plane of M2S in the XRD spectrum of M2S used to manufacture the composite, and the magnitude of the first lattice constant (d1) is 5.78 or greater. Claim 5 A composite cathode active material according to claim 4, wherein the first peak has a first diffraction angle and the second peak has a second diffraction angle, and the first diffraction angle is smaller than the second diffraction angle, or the first peak has a first full width at half maximum (FWHM1) and the second peak has a second full width at half maximum (FWHM2), and the first full width at half maximum is larger than the second full width at half maximum, and the first full width at half maximum is 1° or more. Claim 6 A composite cathode active material according to claim 1, wherein the Mohs hardness of the alkali metal salt and the carbon-based material is greater than that of M2S, and the Mohs hardness of the alkali metal salt and the carbon-based material is each 0.7 or higher. Claim 7 delete Claim 8 A composite cathode active material according to claim 1, wherein the carbon-based material comprises a fibrous carbon-based material, the fibrous carbon-based material comprises a carbon nanostructure, the carbon nanostructure comprises a carbon nanofiber, a carbon nanotube, a carbon nanobelt, a carbon nanorod, or a combination thereof, and the content of the carbon-based material is 1 to 20 wt% of the total weight of the composite. Claim 9 A composite cathode active material according to claim 1, comprising 10 to 80 parts by weight of M2S, 1 to 40 parts by weight of an alkali metal salt, and 1 to 20 parts by weight of a carbon-based material per 100 parts by weight of the composite. Claim 10 A positive electrode comprising: a positive electrode current collector; and a positive electrode active material layer disposed on one or both sides of the positive electrode current collector, wherein the positive electrode active material layer comprises a composite positive electrode active material and a solid electrolyte according to any one of claims 1 to 6 and claims 8 to 9. Claim 11 A cathode according to claim 10, comprising 40 to 90 parts by weight of a composite cathode active material and 10 to 60 parts by weight of a sulfide-based solid electrolyte per 100 parts by weight of the cathode active material layer, wherein the composite cathode active material comprises a carbon-based material, and the carbon-based material is disposed only in the composite cathode active material layer. Claim 12 A solid-state secondary battery comprising: an anode according to claim 10; a cathode; and an electrolyte layer disposed between the anode and the cathode, wherein the cathode comprises a cathode current collector and a first cathode active material layer disposed on one surface of the cathode current collector. Claim 13 A solid-state secondary battery according to claim 12, wherein the first negative electrode active material layer comprises a negative electrode active material and a binder, the negative electrode active material has a particle form, and the average particle size of the negative electrode active material is 4 μm or less. Claim 14 A solid-state secondary battery according to claim 12, wherein the negative electrode active material comprises one or more selected from a carbon-based negative electrode active material and a metal or metalloid negative electrode active material, wherein the carbon-based negative electrode active material comprises amorphous carbon, crystalline carbon, porous carbon, or a combination thereof, and the metal or metalloid negative electrode active material comprises gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), zinc (Zn), or a combination thereof. Claim 15 A solid-state secondary battery according to claim 12, wherein the negative electrode active material comprises a mixture of a first particle made of amorphous carbon and a second particle made of a metal or metalloid, and the content of the second particle is 1 to 60 wt% based on the total weight of the mixture. Claim 16 A solid-state secondary battery according to claim 12, further comprising a second negative electrode active material layer disposed between the negative electrode current collector and the first negative electrode active material layer and between the negative electrode current collector and the electrolyte layer, wherein the second negative electrode active material layer is a metal layer and the metal layer comprises lithium or a lithium alloy. Claim 17 An all-solid-state secondary battery according to claim 12, wherein the electrolyte layer comprises a solid electrolyte, a gel electrolyte, or a combination thereof, the solid electrolyte comprises a sulfide-based solid electrolyte, an oxide-based solid electrolyte, a polymer solid electrolyte, or a combination thereof, and the gel electrolyte comprises a polymer gel electrolyte. Claim 18 In claim 17, the sulfide-based solid electrolyte is Li2S-P2S5, Li2S-P2S5-LiX, where X is a halogen element, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n , m, n are positive numbers, Z is one of Ge, Zn, or Ga, Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q , p, q are positive numbers, M is one of P, Si, Ge, B, Al, Ga, In, Li 7-x PS 6-x Cl x , 0≤x≤2, Li 7-x PS 6-x Br x , 0≤x≤2, and Li 7-x PS 6-x I x One or more selected from , 0≤x≤2, the sulfide-based solid electrolyte comprises an argyrodite-type solid electrolyte, the argyrodite-type solid electrolyte comprises one or more selected from Li6PS5Cl, Li6PS5Br, and Li6PS5I, and the density of the argyrodite-type solid electrolyte is 1.5 to 2.0 g / cc. Claim 19 A solid-state secondary battery according to claim 13, wherein the positive electrode comprises a positive current collector, and one or more of the positive current collector and the negative current collector comprise a base film and a metal layer disposed on one or both sides of the base film, wherein the base film comprises a polymer, wherein the polymer comprises polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polybutylene terephthalate (PBT), polyimide (PI), or a combination thereof, and wherein the metal layer comprises indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or an alloy thereof. Claim 20 A solid-state secondary battery according to claim 13, further comprising an inert member disposed on one side of the anode.
Citation Information
Patent Citations
Full solid state lithium-sulfur / sodium-sulfur battery using halides as electrode active substances and catalysts
CN109509872A
Positive electrode for all-solid secondary battery, method for manufacturing same, and all-solid secondary battery
KR1020170068448A
All Solid secondary battery
KR1020220027499A